Exploring black wheat's nutritional profile and health benefits in metabolic disorders - Mehul Prajapati; Akash Kumar; Sumit Grover; Bhupendra Prajapati; Udaykumar Vegad; Swapnil Borse; Sagar Salave; Dignesh Khunt (Food and Humanity, 2026)

Evolution of high-altitude river-dominated lake deltas, NW Himalaya - Sumit Sagwal; Anil Kumar; Subhojit Saha; Gautam Rawat; Pradeep Srivastava; Choudhurimayum Pankaj Sharma (CATENA, 2026)

Lactobionic acid-enriched yoghurt improves calcium bioavailability and bone mineralization: in vitro and in vivo validation - Shamim Hossain; Yogesh Khetra; Chandni Dularia; Sangita Ganguly; Himanshu Kumar Singh; Sumit Arora; Heena Sharma (Bioactive Carbohydrates and Dietary Fibre, 2026)

Mitochondrial dysfunction–driven inflammation and β-Cell apoptosis in type 2 diabetes mellitus: mechanistic insights and therapeutic implications - Satyam Yadav; Gautam Kumar; Sumit Kumar; Khadga Raj Aran; Sourabh Kosey (Molecular Biology Reports, 2026)

A systematic study of the phosphate-bearing sedimentary rocks of Tehri Garhwal, Uttarakhand: constraining the paleo-redox conditions - Vikash Kumar; Shamim A. Dar; Nozmul Karim; Mohammad Javed; Sumit K. Ghosh (Carbonates and Evaporites, 2026)

Efficacy of micropiles for improvement in performance of soil embankment under rapid drawdown conditions through transient seepage analysis - Sumit Kumar; Abhijit Anand; Rajib Sarkar; Lohitkumar Nainegali (Transportation Geotechnics, 2026)

Highly dispersed Cu on TiO₂ for photoreduction of hexavalent chromium in the presence of glycerol - Srishti; Shweta Kumari; Sumit Kumar Pathak; Abhishikta Chatterjee; Varun Kumar Gupta; Aditya Kumar; Apurba Sinhamahapatra (Journal of Environmental Chemical Engineering, 2026)

UV-C assisted microwave drying of Ashwagandha (Withania somnifera) leaves: Drying kinetics, fuzzy logic-based model evaluation, and selected optical and phytochemical attributes - Sudarshan Ramanathan; S. Samuel Nirmalsingh; P. Dinesh Kumar; Sumit Sudhir Pathak (Innovative Food Science & Emerging Technologies, 2026)

Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Chlorophyll-a and phytoplankton community responses to cyclone Dana in the coastal waters of the north-western Bay of Bengal - Amit Kumar Jena; Kamal Kumar Barik; Sumit Kumar Mohanty; Suchismita Sahu; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Alakes Samanta; Pratap Kumar Chhotaray; Sudheer Joseph; T. M. Balakrishnan Nair (Spatial Information Research, 2026)

Quorum sensing–mediated infochemical dialogue in the rhizosphere: Implications for plant stress resilience - Riti Pal; Rohini Verma; Sumit Kumar; Jangila Hazowary; Jayajeevitha SRM; Aayeisha Das; Aarti Bairwa; Debasis Mitra; Ali Chenari Bouket; Masoud Chamani; Udai B. Singh; R. Arutselvan; et al. (Rhizosphere, 2026)

Adaptation and mitigation approaches to reduce heat-related health risks: An overview of systematic reviews - Awakash Turkar; Sumit Aggarwal; Kakali Purkayastha; Ram Surath Kumar; Pragati Agarwal; Vikas Dhiman; Farah Naaz; Ila Agnihotri; Sanghamitra Pati (Environmental Research, 2026)

Occupational exposure to respirable crystalline silica and its association with pulmonary function impairment among coal mine workers: A retrospective assessment - Manish Yadav; Nitin Kumar Singh; Tanveer Rehman; Sanghamitra Pati; Vinita Arora; Sumit Saha (Environmental Research, 2026)

Iso-conversional kinetic modeling and pyrolysate compositional analysis of Chlorella minutissima for optimized bio-crude production via fast pyrolysis - Santoshnambi Yadav; Satyanarayana Reddy Battula; Sumit Kumar; Suryendu Dutta; Ramkrishna Sen (Bioresource Technology Reports, 2026)

Retrieval of wheat crop growth variables with novel frequency difference vegetation indices - Dileep Kumar Gupta; Sumit Kumar Chaudhary; Prashant K. Srivastava; Rajendra Prasad; Dharmendra Kumar Pandey (Advances in Space Research, 2026)

Characterisation of mineral dust particles amidst sand and dust storm occurring in The Thar Desert Region - Mamta Devi; Sumit Kumar Mishra; Sudhir Husale; Gounda Abdul Basheed; Aamir Khan; Rishabh Singh; Kartika Pandey; Supreet Kaur; Mandeep Kaur (Arabian Journal of Geosciences, 2026)

Exogenous kinetin mitigates arsenic-induced oxidative stress by regulating ROS homeostasis and antioxidant defense in Ocimum basilicum L. - Asif Hussain Hajam; Mohd Soban Ali; Sumit Kumar Singh; Umra Sheikh; Gausiya Bashri (Plant Cell Reports, 2026)

Molecular crosstalk in oil palm–Ganoderma interactions: lignin breakdown and basal stem rot progression - Amrutha Lakshmi M; Arutselvan R; Andrea Susan Baby; Javeedvali S; Amjada S. Khan; Pradeep Manyam; Nirmal Sudhir Kumar Harsh; Sumit Kumar; Rohini Verma (Plant and Soil, 2026)

Slope stability analysis of Mount St. Helens slope using Scoops3D and machine learning - Sumit Kumar; Jirapon Sunkpho; Divesh Ranjan Kumar; Warit Wipulanusat (Transportation Geotechnics, 2026)

Role of urban discharges in regulating the dynamics of river water quality to antibiotic resistance in subtropical river basins - Niteesh Kumar Pandey; Alaa Eddin Alhmeidi Alkhatib; Monika Simon; Rajesh Kumar Vishwakarma; Jagdeesh Kumar; V. Srikanth; Sumit Sen; Himanshu Joshi; Shweta Yadav; Javier Mateo-Sagasta; Mahesh Jampani; Alok Sikka; et al. (Journal of Environmental Management, 2026)

A critical appraisal of anti-hyperglycemic mechanisms, matrix-dependent bioavailability, and species-stratified safety of Cinnamomum spp. as functional food ingredients - Acharya Balkrishna; Sharad Kumar Tripathi; Sumit Kumar Singh; Sonam Verma; Vedpriya Arya (Food Research International, 2026)

Corrigendum to “Exploring black wheat's nutritional profile and health benefits in metabolic disorders” [Food and Humanity 7 (2026) 101375] - Mehul Prajapati; Akash Kumar; Sumit Grover; Bhupendra Prajapati; Udaykumar Vegad; Swapnil Borse; Sagar Salave; Dignesh Khunt (Food and Humanity, 2026)

Can Micro-Irrigation in Canal Command Areas Increase Water Use Efficiency? A Feasibility Study for Sustainable Water Resources - Sandeep Kumar Chourasia; Sumit Kumar Vishwakarma; Ashish Pandey (Water Conservation Science and Engineering, 2026)

Development and Optimization of PLGA-PVA Nanoparticles Encapsulating Silymarin for Pulmonary Delivery and TRPV4 Modulation - Mohit Kumar; Md. Kamaruz Zaman; Pakter Niri; Subramanyam Polopalli; Piya Adhikari; Amartya Banerjee; Ajay Kakati; Shriyansh Srivastava; Danswrang Goyary; Yangchen Doma Bhutia; Sanjeev Karmakar; Sumit Kishor; et al. (Journal of Pharmaceutical Innovation, 2026)

Shaping SHAPE - A spectro-polarimeter onboard Chandrayaan-3 to observe Earth as an Exoplanet - Anuj Nandi; Swapnil Singh; Bhavesh Jaiswal; Anand Jain; Smrati Verma; Reenu Palawat; B.T. Ravishankar; Brajpal Singh; Priyanka Das; Supratik Bose; Supriya Verma; Waghmare Rahul Gautam; et al. (Advances in Space Research, 2026)

Deposition of Particulate Matter on Roadside Plant Leaves in Urban Environment (New Delhi): Implications to Plant Health - Supreet Kaur; Neha Gandhi; Sumit Kumar Mishra; Amit Kumar Goswami; Vikas Goel; Mamta Devi; Kartika Pandey (Aerosol Science and Engineering, 2026)

Tunable Emission in Samarium(III) Complexes for Display Applications: Synthesis, Structural Features and Optoelectronic Investigation - Sonia Redhu; Devender Singh; Swati Dalal; Kapeesha Nehra; Sumit Kumar; Rajender Singh Malik; Parvin Kumar; Jayant Sindhu (Journal of Fluorescence, 2026)

Double-edged sword of fungicides: non-target and harmful effects and their management for eco-friendly agriculture - Sanjay Kumar Goswami; Ranjit Singh Gujjar; Rajeev Kumar; Rahul Kumar Tiwari; Hillol Chakdar; Prassan Choudhary; Saket Kumar; Sumit Kumar; Mala Kumari (Indian Phytopathology, 2026)

Bioefficacy of plant growth promoting rhizobacteria (PGPR) in the sustainable management of root-knot nematodes in eggplant - Megha Sharma; Sunita Devi; Sumit Vashisth; Dharmendra Kumar; Subhash Chand; Kumari Manorma; Rakesh Kumar; Parmod Verma; Balbir Singh Dilta; Abhay (Physiological and Molecular Plant Pathology, 2026)

Productivity, carbon dynamics and soil fertility of eucalyptus based agroforestry system under different winter crops - Rakesh Panday; Dipty Kumar Das; Rajesh Kumar Meena; Soibam Lanabir Singh; Santosh Kumar Singh; Ritwik Sahoo; Prabhat Tiwari; Sumit Sow; Dibyajyoti Nath; Shivani Ranjan (Plant and Soil, 2026)

Analysis of microsatellites (SSRs) of Curvularia geniculata strain SKG23 isolated from leaf spot disease of Mentha (Mentha arvensis L.) - Sumit Kumar Polley; Swapan Kumar Ghosh (Vegetos, 2026)

Decoding the Impact of Acidification and Toxic Metal Stress on Tea Soil Bacteriome: Integrating 16S rRNA Sequencing with Multivariate Approaches - Riddhi Basu; Sonali Banerjee; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Pradip Bhattacharyya (Biological Trace Element Research, 2026)

Recent Trends in Criteria Air Pollutants and Black Carbon Over the Western Indo-Gangetic Plain Using Ground-Based and Satellite Observations - Anirudh Tomar; Sumit Pokhariyal; Prashant Kumar Chauhan; Sanjeev Kumar; Alok Sagar Gautam; Sneha Gautam; Vijay Kumar; Parmanand Prakash Pathak (Aerosol Science and Engineering, 2026)

Harnessing hemicellulose: A systematic review of its role in bioethanol and value-added product synthesis from lignocellulosic feedstocks - Diksha Sawhney; Sumit Sharma; Meenu Singh; Prabhat Kumar; Roma Pandey (Bioresource Technology Reports, 2026)

Spatial mapping of rice leaf area index using UAV-borne RGB and multispectral data: a comparison of Beer-Lambert law and machine learning algorithms - Sumit Kumar Vishwakarma; Kritika Kothari; Ashish Pandey (Modeling Earth Systems and Environment, 2026)

3D reliability assessment of railway embankment under pore-water pressure and seismic loading using supervised machine learning models - Brijbhan Rao; Divesh Ranjan Kumar; Sumit Kumar; Warit Wipulanusat; Avijit Burman; Lal Bahadur Roy (Modeling Earth Systems and Environment, 2026)

Comprehensive evaluation of surface water quality: heavy metals, speciation, and human health risks in an industrial region of West Bengal, India - Gourav Mondal; Riddhi Basu; Sumit Kumar; Shreya Chakraborty; Ambika Barman; Kasturi Charan; Jajati Mandal; Pradip Bhattacharyya (Environmental Monitoring and Assessment, 2026)
This study evaluates the hydrogeochemical characteristics, heavy metal (HM) contamination, irrigation suitability, and associated human health risks of surface water in an industrial area affected by dye-manufacturing activities in West Bengal, India. A total of 30 surface water collected in triplicate were analysed. Major ions were determined using standard American Public Health Association (APHA) methods, HMs were quantified using atomic absorption spectrometry (AAS), and aqueous speciation was modelled using Visual MINTEQ. The water was slightly alkaline, with pH values ranging from 7.18 to 8.92 (mean 7.79±0.41). Extremely high salinity was observed, as electrical conductivity ranged from 2500 to 21,000 μS cm⁻¹ (mean 11,300±4272 μS/cm), while total dissolved solids varied between 1500 and 12,600 mg/L (mean 6780 ± 2563 mg/L), exceeding World Health Organization (WHO) guideline values. Major cations followed the order Ca²⁺ > Mg²⁺ > Na⁺ > K⁺, whereas dominant anions were HCO 3 ⁻ > Cl⁻ > SO 4 2 ⁻, reflecting combined geogenic and anthropogenic influences. Mean concentrations of heavy metals were elevated, with values of Cr (0.97 mg/L), Pb (0.23 mg/L), Ni (0.19 mg/L), Cu (0.06 mg/L), and Cd (0.004 mg/L). Except for Cu, all metals exceeded WHO permissible limits, indicating substantial contamination. Pollution indices (Pi) confirmed severe degradation, with Pi > 1 for Pb, Ni, Cr, and Cd. High average values of C d (48.89), Heavy Metal Evaluation Index (HEI), 53.65, and Heavy Metal Pollution Index (HPI), 338.73, indicated high to extreme pollution, while Water Pollution Index (WPI) values (1.51–5.27) classified all samples as severely polluted. Speciation modelling showed Cd predominantly occurred as Cd 2+ (52.35%) and CdCl + (32.10%), suggesting high mobility. Lead (Pb) was predominantly present as PbCO 3 (aq) (39.47%) and PbHCO 3 + (31.31%), Ni largely as Ni 2+ (63.15%), and Cr(VI) mainly as CrO 4 2 ⁻. Copper was largely present as CuCO 3 (aq) (67.94%). Irrigation indices indicated suitability, although overall water quality remained poor. Human health risk assessment identified Pb and Cr as posing non-carcinogenic risks, while Cr presenting the highest carcinogenic risk, particularly for children (CR > 1 × 10⁻ 4 ). Overall, the findings highlight severe surface water degradation and underscore the urgent need for remediation measures and stricter regulatory intervention.

Unveiling the glucan profile: a comparative study of Lion’s Mane and Shiitake mushrooms - C. S. Keerthana; Rozy Kumari; Muskan Beura; Sumit Sharan; Susheel Kumar Sharma; Ananta Ganjoo; Anil Dahuja; Veda Krishnan (Natural Product Research, 2026)

Coupled role of Westerlies and Indian Summer Monsoon in the climatic variability of Kashmir Valley, NW India during the Late Quaternary - Shirish Verma; Binita Phartiyal; Shailesh Agrawal; P. Morthekai; M.C. Manoj; Rakesh Chandra; Lakhi Narayan Sahu; Sumit Sagwal; Pankaj Kumar; Abhayanand Singh Maurya (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effect of sodium hexametaphosphate and trisodium citrate on the heat stability, rheological and functional properties of microfiltered retentate of buffalo milk - Bhaskara K. Govindappa; Bhumkar Prajwal Vilas; Ganga Sahay Meena; Sumit Arora; Heena Sharma; Ashish Kumar Singh; Gaurav Kr Deshwal (International Dairy Journal, 2026)

Corrigendum to application of tamarind (Tamarindus indica L.) kernel powder as a functional ingredient in chocolate: Process optimization and multidimensional characterization [Food and Humanity 6 (2026) 1–13/100988] - Nitigya Verma; Pushpanjali Purohit; Ankita Dobhal; Richa Bhtoya; Ritesh Mishra; Sumit Jadaun; S.H. Akbari; Sanjay Kumar (Food and Humanity, 2026)

Application of tamarind (Tamarindus indica L.) kernel powder as a functional ingredient in chocolate: Process optimization and multidimensional characterization - Nitigya Verma; Pushpanjali Purohit; Ankita Dobhal; Richa Bhtoya; Ritesh Mishra; Sumit Jadaun; S.H. Akbari; Sanjay Kumar (Food and Humanity, 2026)

Assessing the geochemical impacts of bauxite mining to the neighbouring environment: a quantitative approach through risk assessment, sensitivity analysis and source apportionment of heavy metals - Mohammad; Gourav Mondal; Saibal Ghosh; Sumit Kumar; Pradip Bhattacharyya (Environmental Geochemistry and Health, 2026)

Synergistic effect of indigenous endophytes to boost nutritional content, quality traits and yield in tomato - K. R. Nayana; Sumit Deswal; Satish Kumar; Rahul Kumar Dhaka; Arvind Pratap Singh; Anuj Rana (Antonie van Leeuwenhoek, 2026)

DFT-Assisted Optical Emission Analysis of Green Luminescent Terbium(III) Mononuclear Complexes with BPTD and N-Donor Chelates - Swati Dalal; Devender Singh; Vandana Aggarwal; Anjli Hooda; Vandna Nishal; Sumit Kumar; Rajender Singh Malik; Parvin Kumar; Jayant Sindhu (Journal of Fluorescence, 2026)

Integrated chemo-enzymatic strategy for production of functional xylooligosaccharides from sunflower stalk biomass - Mahak Gupta; Ridhika Bangotra; Surbhi Sharma; Bisma Habib; Arpana Thakur; Priya Singh; Muskaan Chib; Parushi Nargotra; Vishal Sharma; Nisha Kapoor; Ritu Mahajan; Sumit G. Gandhi; et al. (World Journal of Microbiology and Biotechnology, 2026)

Human reproductive exposure to microplastics: A multi-technique analytical study of menstrual and amniotic fluids - Girish Chandra Sharma; Neeraj Kumar; Damini Devrukhkar; Rahul Mulchandji Joshi; Sourav Debnath; Bhumi Chaturvedi; Sumit Rajotiya; Shivang Mishra; Anupama Sharma; Mahaveer Singh; Deepak Nathiya; Balvir Singh Tomar (NanoImpact, 2026)

Harnessing the anti and pro-oxidants potential of selenium - Dibyajyoti Nath; Sayali Biradar; Sumit Sow; Shiva Nath Suman; Vipin Kumar; Shivani Ranjan; Santosh Kumar Singh; Hemlata Singh; Ranjan Laik; Mainak Ghosh; Lalita Rana (Journal of Trace Elements in Medicine and Biology, 2026)

Molecular recognition in PVDF–Montmorillonite–GO hybrid membranes for precision pollutant removal and fouling resistance - Triparna Chakraborty; Dharmveer Yadav; Rohan Mondal; Manoj Kumar Pandey; Sumit Saxena; Shobha Shukla (Journal of Environmental Chemical Engineering, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Intensification of rice-wheat cropping system with summer green gram improves growth, productivity and profitability of rice in the middle Indo-Gangetic Plains of India - Manish Raj; Sushant; Mainak Ghosh; Anil Kumar Singh; Sumit Sow; Sanjay Kumar; Birendra Kumar; Swaraj Kumar Dutta; Nintu Mandal; Pritam Ganguly; Arnab Roy Chowdhury; Shishpal Poonia; et al. (European Journal of Agronomy, 2026)

Ten questions on indoor greening and environmental quality - Prashant Kumar; Hao Sun; Akash Biswal; Anubhav Kumar Dwivedi; Ho Yin Wickson Cheung; Kamaldeep Bhui; Tijana Blanusa; Bert Blocken; Nicole van den Bogerd; John Kaiser Calautit; Nicola Carslaw; Brian Considine; et al. (Building and Environment, 2026)

Deciphering Long-Term Variation of Aerosol Characteristics and Their Climatic Implication over the World’s Wettest Place: Mawsynram - Mamta Devi; Sumit Kumar Mishra; Kartika Pandey; Supreet Kaur; Anikender Kumar; Vijay Kumar Soni; Amarendra Singh; Atul Kumar Srivastva (Journal of the Indian Society of Remote Sensing, 2026)

Deciphering stone mining-induced hazardous heavy metal contamination in agricultural soils using source attribution, health-dietary risk analysis, and machine learning-driven insights - Annewsa Acharya; Chetana Tunga; Sonali Banerjee; Riddhi Basu; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Shreya Chakraborty; Gopinath Gorai; Sudipta Tripathi; Pradip Bhattacharyya (Environmental Geochemistry and Health, 2026)

Pseudomonas Pichavaramensis sp. nov., Isolated from Brackish Water of Pichavaram Mangrove forest, Tamil Nadu - Sumit Mittal; Hariom Kushwaha; Nandini; Stanzin Choksket; Devachandana C. Prabhu; Anil Kumar Pinnaka; Suresh Korpole (Current Microbiology, 2026)

Reliable Model Development of Density for Pure Biofuels via Data Driven Approaches - Mahran Al-Zyoud; Magdi E. A. Zaki; Raed Alfilh; Gadug Sudhamsu; Prabhat Kumar Sahu; Murari Devakannan Kamalesh; Sumit Sharma; Sobhi M. Gomha; Nargis Yousafzai (BioEnergy Research, 2026)

A deep learning mobile application for tomato leaf nutrition deficiency identification with YOLOv8 and enhanced augmentation - Kamaldeep Joshi; Varun Kumar; Sumit Kumar; Kriti Katyal; Rainu Nandal; Ashima Nehra; Kashmir Singh; Narendra Tuteja; Ritu Gill; Sarvajeet Singh Gill (Plant Science, 2026)

Harnessing teosinte for quality traits enhancement and genetic diversity in maize - Pardeep Kumar; Mukesh Choudhary; Seema Sheoran; Bhupender Kumar; Sushil Kumar; Ankush Sharma; Bharat Bhushan; Bahadur Singh Jat; Dharam Paul; Sumit Kumar Aggarwal; Shyam Bir Singh (Cereal Research Communications, 2026)

Unravelling the role of soil enzymatic activity as a vital bioindicator of soil health and fertility in agricultural systems - Ingudam Bhupenchandra; L. Devarishi Sharma; Menaka Devi Salam; Sumit Kumar; S.K. Chongtham; Anil K. Choudhary; H. Lembisana Devi; Soibam Sinyorita; Pranab Dutta; Ali Chenari Bouket; Tatiana Minkina; Chetan Keswani (Applied Soil Ecology, 2026)

Stacking ensemble for improved landslide susceptibility mapping in Darjeeling Himalayas, India - Sumit Kumar; Gargi Singh; Rabisankar Karmakar; Akshaya Kumar Mishra (Journal of Earth System Science, 2026)

Biological green synthesis of nanoparticles: A sustainable platform for agricultural, environmental, food, and cosmetic applications - Shruti S. Raut; Arpit Sharma; Ravi Yadav; Sumit Kumar; Alok Shukla; Amit Singh; Abha Mishra (Journal of Environmental Chemical Engineering, 2026)

Tracing environmentally hazardous metal pollution in iron mine-influenced agro-ecological regions: Insights from soil quality indices, source attribution, and health-risk appraisal - Debatri Dewanjee; Sumit Kumar; Sonali Banerjee; Gourav Mondal; Saibal Ghosh; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2026)

Synergy between Piriformospora Indica and Salicylic Acid Modulates Maize Stress Physiology, Ultrastructure, and Gene Expression - Sunil K. Singh; Rakesh Pandey; Chanda Panwar; Pankaj Kumar; Sumit Sharma; Sonali Batra; Pradeep Kumar; Jai Gopal Sharma; Madhulika Singh; Bhoopander Giri (Journal of Plant Growth Regulation, 2026)

Exposure assessment of respirable free silica in coal mining areas - Manish Yadav; Nitin Kumar Singh; Sumit Saha (Environmental Geochemistry and Health, 2026)

Advanced integrated Eco-strategies for effective antibiotic waste management - Varsha Sharma; Ishfaq Nabi Najar; Anu Radha; Sonali Sharma; Sunil Kumar; Deepika Singh; Sumit G. Gandhi; Vinod Kumar (Biodegradation, 2026)

Translational reprogramming of Zea mays-fed larval midgut of Spodoptera litura indicates non-adaptive response - Archana Singh; Sumit Kumar; Kalpesh Nath Yajnik; Sujata Singh; Indrakant Kumar Singh (Arthropod-Plant Interactions, 2026)

Optimizing the Litchi (Litchi chinensis L.) Harvest Window Through Potassium Nitrate and Gibberellic Acid Applications Under North-West Bihar Conditions - Dhiru Kumar Tiwari; Bharati Upadhaya; R. K. Tiwari; Sumit Kumar Singh; Saurabh Dubey; Chelpuri Ramulu; A. P. Singh; Ashish Kumar Rai (Applied Fruit Science, 2026)

What are we missing? A systematic mapping of climate change projections in the Brahmaputra River Basin - Rupam Bhaduri; Sumit Vij; Anamika Barua; Arup Kumar Sarma (Climate and Development, 2026)

Understanding the influence of landcover on spring dynamics and evaporation, in Himalayan region, using stable isotope and discharge - Neeraj Pant; Dharmappa Hagare; Basant Maheshwari; Shive Prakash Rai; Abhinav Patel; Nijesh Puthiyottil; Sharad Kumar Jain; Lakhi Narayan Sahu; Sumit Sen; Mayank Upadhyay (Science of The Total Environment, 2026)

Exploring microbial diversity, antibiotic resistance, and their environmental drivers in urban and peri-urban riverbed sediments of sub-tropical river basins - Niteesh Kumar Pandey; Monika Simon; Rajesh Kumar Vishwakarma; Sumit Sen; Himanshu Joshi; Shweta Yadav; Javier Mateo-Sagasta; Mahesh Jampani; Alok Sikka; Saugata Hazra (Environmental Research, 2026)

Graphene wrapped hollow vanadium oxide nanospheres as anode for Li-ion supercapacitors - Arun Kumar Singh; Shobha Shukla; Sumit Saxena (Chemical Engineering Journal, 2026)

Urban dimension of microplastics in municipal solid waste compost within an emerging eastern Indian city - Sibadutta Mohanty; Manish Kumar; Kushalindu Biswas; Arati Ray; Akshyurna Pattnaik; Chandrama Dipa; Sumit Saha (Water, Air, & Soil Pollution, 2026)

Seasonal variability and temperature-driven temporal dynamics of air pollutants in a mega coal mining zone of the talcher coalfield - Artatrana Mishra; Sarat Chandra Sahu; Manish Yadav; Nitin Kumar Singh; Charu Jhamaria; Amit Karmakar; Sumit Saha (Environmental Geochemistry and Health, 2026)

Geochemistry and U–Pb Geochronology of Volcaniclastic Rocks From the NW Lesser Himalayan Sequence: Implications for Arc‐Related Tectonic Setting at Northern Proto‐Indian Continental Margin During the Neoproterozoic - Subhojit Saha; Kaushik Das; Shivani S. Choudhari; Abhishek Kumar Pandey; Shruti Ranjan Mishra; Sumit Kumar Ghosh; Alok Deep; Partha Pratim Chakraborty (Island Arc, 2026)
The protracted tectonic history concerning the northern edge of the pre‐Himalayan proto‐Indian plate margin during the Neoproterozoic time has been a long‐standing subject of debate, with various hypotheses enduring over several decades. Although a continental rift to passive margin setting has been proposed for the deposition of Neoproterozoic rocks of the Outer Lesser Himalayan Sequence (OLHS), the similarity in detrital zircon age peaks and Nd isotope values of OLHS rocks with those of the Higher Himalayan Crystalline Sequence (HHCS) led to the proposition of an arc‐related setting. So far, there is no such report of Neoproterozoic arc‐related magmatism from the Lesser Himalayan Sequence. In the present study, an interbedded volcaniclastic horizon has been identified from the basal stratigraphic level of the Nagthat Formation, OLHS. Geochemistry and U–Pb zircon geochronology are used to understand the provenance and tectonic setting of the Nagthat volcaniclastic rock. The angularity of the framework minerals, moderate degree of weathering (avg. Chemical Index of Alteration value 62), and immature nature (Index of Compositional Variability 1–1.1) suggest that a contemporaneous volcanic province was probably the main source. Whole rock geochemical analysis shows high Th/Sc (1.67–3.40, avg. 2.71), La/Sc (4.74–8.21, avg. 7.14), and low Cr/Th ratios (1.78–5.45, avg. 3.02). It supports that the volcaniclastic was supplied from an acid to intermediate source rocks, such as rhyolite and dacite/andesite. U–Pb detrital zircon analysis yielded a major age peak around 775 Ma. However, comparison of the U–Pb zircon age data with published datasets from the Lower (Chandpur Formation) and upper (Nagthat Formation) stratigraphic horizons suggests a timing of volcanism between 800 and 700 Ma. Geochronological and geochemical characteristics of the volcaniclastic rock suggest a signature transitional from passive to active continental margin setting, indicating that at least subduction was ongoing during the Tonian (800–700 Ma) at the northern proto‐Indian plate margin.

Mechanisms and modalities of herbal anti-fertility: toward integrative reproductive health solutions - Manoj Kumar Mishra; Sumit Sharma; Shivangi Sharma; Sagar Pamu (Advances in Traditional Medicine, 2025)

Unveiling the synergistic impact of heavy-metals and alkalinity on microbial diversity using machine learning techniques - Gourav Mondal; Sonali Banerjee; Saibal Ghosh; Sumit Kumar; Pradip Bhattacharyya (Environmental Sustainability, 2025)

Raindrop size distribution in stratiform precipitation: Insights from spectral bin simulations over the high-altitude cloud physics observatory, Western Ghats - Sumit Kumar; E.A. Resmi; Dharmadas Jash; Sachin Patade; R.K. Sumesh; Anusha Andrews; Nita Sukumar; A.R. Aswini; Gayatri Kulkarni (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Influence of multi-enzyme approach and spray drying on physico-chemical, browning and protein digestibility of lactose-hydrolyzed milk powder - Payal Singh; Sumit Arora; Deepika Kathuria; Richa Singh; Priyanka Singh Rao; Vivek Sharma; Ashish Kumar Singh (Food and Humanity, 2025)

Moisture build-up and thermodynamic processes in precipitation regimes during the southwest monsoon over a tropical coastal region - Anusha Andrews; E.A. Resmi; R.K. Sumesh; Sneha Sunil; A.R. Aswini; Nita Sukumar; Sumit Kumar; A. Sabarinath; Tejavath Charan Teja; Dharmadas Jash (Dynamics of Atmospheres and Oceans, 2025)

Co-infection with systemic candidiasis and diphtheritic aspergillosis in a Buffalo calf - Sumit S. Kamble; Veena R. Sutar; S. D. Vinay Kumar; Sonu S. Nair; V. Athira; J. Pranathi; Pawan Kumar; Prasad Thomas; Bablu Kumar; Premanshu Dandapat; Vidya Singh; Abhishek (Veterinary Research Communications, 2025)

Estimation of wheat and paddy yield in the parts of Indian Punjab by integrating climate and Landsat satellite data using machine learning algorithms - Shikha Sharda; Raj Setia; Sumit Kumar; Mohit Arora; Brijendra Pateriya (Spatial Information Research, 2025)

Deciphering aptamer-protein interactions for bovine sperm sorting through in silico and in vitro studies - Sumit Kumar Singh; Manya Mathur; Himanshu Kamboj; Jai Kumar Kaushik; Ashok Kumar Mohanty; Sudarshan Kumar (Molecular Biology Reports, 2025)

Unlocking the Potential of Arbuscular Mycorrhizal Fungi: Exploring Role in Plant Growth Promotion, Nutrient Uptake Mechanisms, Biotic Stress Alleviation, and Sustaining Agricultural Production Systems - Ingudam Bhupenchandra; Sunil Kumar Chongtham; Ayam Gangarani Devi; Pranab Dutta; Manas Ranjan Sahoo; Sansuta Mohanty; Sumit Kumar; Anil K. Choudhary; Elangbam Lamalakshmi Devi; Soibam Sinyorita; Soibam Helena Devi; M. Mahanta; et al. (Journal of Plant Growth Regulation, 2025)

Unraveling the Seed Bio-priming Contours for Managing Plant Health - Sumit Kumar; R. Arutselvan; K. Greeshma; Shrey Bodhankar; A. U. Akash; Vurukonda Sai Shiva Krishna Prasad; Yasser Nehela; Udai B. Singh; Ingudam Bhupenchandra; Arnab Sen; Laxman Singh Rajput; Marina Burachevskaya; et al. (Journal of Plant Growth Regulation, 2025)

Formulation and Development of HPMC-Based Matrix Dispersion of Atorvastatin-Phospholipid Complex for Attenuation of Hyperlipidaemic Activity in High Fat Diet Induced Rat Model - Durga Uniyal; Sumit Durgapal; Elphine Prabahar; Lata Bisht; Prashant Kumar; Gauree Kukreti (Journal of Pharmaceutical Innovation, 2025)

The Potential of Fungal Endophytes in Plants: Sources of Bioactive Compounds - Sagar Vishwakarma; Vijeta Chaudhry; Sumit Chand; Kalpana Sagar; Kartikey Kumar Gupta; Nitin Bhardwaj; Rajendra Prasad; Pankaj Kumar; Harish Chandra (Indian Journal of Microbiology, 2025)

Differential miRNA expression and regulatory mechanisms in pigmentation and fiber development of white and brown cotton (Gossypium hirsutum) - Sagar Prasad Nayak; Priti Prasad; Shafquat Fakhrah; Debashree Pattanaik; Sumit Kumar Bag; Chandra Sekhar Mohanty (Functional & Integrative Genomics, 2025)

Hydrogeochemical and health risk assessment of groundwater quality in calcareous zones using a novel multimodal statistical approach - Gourav Mondal; Sumit Kumar; Rupsha Nandi; Pradip Bhattacharyya (Environmental Geochemistry and Health, 2025)

Harnessing vermicomposted chromite-asbestos mine waste for sustainable chilli production: a focus on biochemical traits and yield enhancement with machine learning insights - Sonali Banerjee; Sonam Jha; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Pradip Bhattacharyya (Clean Technologies and Environmental Policy, 2025)

RNA interference (RNAi) for insect pest management: understanding mechanisms, strategies, challenges and future prospects - Deepak Kumar Mahanta; J. Komal; Tanmaya Kumar Bhoi; Ipsita Samal; Sangeeta Dash; Sumit Jangra (Biologia Futura, 2025)

Impact of Preharvest Bagging on Fruit Physiology and Quality of Mango (Mangifera indica L.) Under Subtropical Conditions - Dinesh Kumar; K. Kishore; K. K. Srivastava; A. Singh; M. Mishra; P. K. Shukla; T. Damodaran; Sumit K. Soni (Applied Fruit Science, 2025)

Ferrite nano-coating for rapid sustainable desalination using solar stills - Kousik Pradhan; Vikash Kumar Chauhan; Dharmveer Yadav; Amrit Kumar Thakur; Shobha Shukla; Siddhartha P. Duttagupta; Sumit Saxena (Desalination, 2025)

Bi-functional carbonaceous hybrid nanocomposites with anticancer and antibacterial potential: synthesis, characterization, and cytotoxicity assessment - Juhi Saxena; Tarun Kumar Upadhyay; Anupam Jyoti; Unnati Joshi; Anand Joshi; Mahendra Singh Rathore; Sanketsinh Thakor; Jaivik Pathak; Sumit Das Lala; Payel Deb (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Impact of weather parameters and integrated disease management practices on banded leaf and sheath blight (caused by Rhizoctonia solani f. sp. sasakii) and grain yield of maize - Parvesh Kumar; Rakesh Mehra; Poonam Kumari; Prashant Chauhan; Rakesh Kumar; Harbinder Singh; Vishal Gandhi; Mahaveer Singh Bochalya; Ashish Jain; Sumit (European Journal of Plant Pathology, 2025)

Timescale of evolution of a late archean collision zone from Coorg, S. India: constraints from zircon and garnet geochronology - Sampriti Basak; Aitor Cambeses; Sumit Chakraborty; Axel Gerdes; Carsten Münker; Ina Martinet; Somnath Dasgupta; Santanu Kumar Bhowmik (Contributions to Mineralogy and Petrology, 2025)
Petrology, geochemistry and geochronology of a metapelite (sillimanite-garnet-biotite-plagioclase-quartz) from the vicinity of the Archean Mercara Shear Zone in Coorg, S. India show that metamorphism at temperatures > 850 °C occurred between 2700–3300 Ma (Phase equilibria, thermobarometry, U-Pb dating of zircons and Lu-Hf dating of garnets). Subsequently, the rocks experienced thermal events at lower temperatures at 2400-2600 Ma as well as at 600-640 Ma (U-Pb dates from rutile). There are indications of multiple episodes of metasomatic/ (high temperature) hydrothermal activity during the Archean events. Residence of the rocks at lower temperatures between the high temperature events is indicated by the kinetics of dissolution of zircon in melt. Taken together, this history shows that (a) P-T-t evolution in this Archean collisional setting happened along an overall clockwise path but not in a single continuous loop - episodes at high temperatures were interspersed with residence at cooler temperatures in between, (b) subtle effects of metamorphism that occurred at temperatures below the peak temperature could help to resolve some controversies related to tectonothermal reconstructions in the region (e.g. whether signatures of both - amalgamation of Dharwar and Coorg cratons and activity along an equivalent of the Betsimisaraka suture zone in east-central Madagascar may be present in the region), and (c) the duration of high-temperature events (several 100 million years at ~ 800 °C) are consistent with an early Earth peel-back style of plate tectonics, rather than modern day plate tectonics, operating in the region at the time.

Integrative study on Meizotropis pellita (Hook. f. ex Prain): phytochemistry, antibacterial potential, molecular insights, biological applications, and conservation strategies of a critically endangered Himalayan endemic plant - Arti Bisht; Balwant Rawat; Janhvi Mishra Rawat; Sumit Purohit; Sanjay Kumar (Vegetos, 2025)

Influence of submergence ratio on scour morphology around spur dike: experimental and numerical analysis - Sai Guguloth; Abhimanyu Roy Chaudhuri; Niloufar Shafighi; Sumit Kumar (Acta Geophysica, 2025)

Whole genome sequencing, assembly and annotation of Curvularia geniculata strain SKG23 isolated from leaf spot disease of mentha (Mentha arvensis L.) - Swapan Kumar Ghosh; Sumit Kumar Polley (Vegetos, 2025)

Intercomparison of machine learning models for estimating leaf area index of rice using UAV-based multispectral imagery - Sumit Kumar Vishwakarma; Benu Bhattarai; Kritika Kothari; Ashish Pandey (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Source apportionment and risk assessment of heavy metals in mangrove soils using multivariate and sensitivity analyses - Annewsa Acharya; Debatri Dewanjee; Gourav Mondal; Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Riddhi Basu; Sumit Roy; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2025)

Excellent electrochemical activities of Sn doped In2S3 with microflower morphology for CO2 reduction to formic acid and methanol - Guruprasad Bhattacharya; Radhapada Manna; Puspendu Sardar; Sibsankar Rahut; Sumit Kumar; Amar Nath Samanta (Journal of Environmental Chemical Engineering, 2025)

Biofortified vermicompost: Exploring bacterial community dynamics and enzymatic pathways through bacteriome analysis for arsenic bioremediation in mine waste - Shreya Chakraborty; Sonali Banerjee; Sumit Kumar; Saibal Ghosh; Pritam Mukherjee; Souvik Das; Pradip Bhattacharyya (Environmental Pollution, 2025)

Zinc fertilization and bud chip transplanting: Effects on zinc fractions, uptake and sugarcane productivity in calcareous soils - Navnit Kumar; Lalita Rana; Vipin Kumar; Sumit Sow; Gangadhar Nanda (European Journal of Agronomy, 2025)

Probing a Blue Button Jellies Beach Stranding Event on the East Coast of India - Kamal Kumar Barik; Amit Kumar Jena; Sumit Kumar Mohanty; Suchismita Srichandan; Sanjiba Kumar Baliarsingh; Alakes Samanta; Pratap K. Chhotaray; Sudheer Joseph; T. M. Balakrishnan Nair (Journal of the Indian Society of Remote Sensing, 2025)

Mitigating dust deposition effects on solar panels: an experimental approach using hydrophobic coating and vibration - Himanshu Kumar; Sandeep Yadav; Abhilasha Chaudhary; Sumit Sharma; Anita Kuradiya (Environmental Science and Pollution Research, 2025)

Marine Derived Edible Films from Seaweed–Fish Protein Composites for Next-Generation Active Packaging - Sarika Kunnath; Bindu Jaganath; Fathima Sameeha K K; Anupama T K; Sreejith S; Ashish Kumar Jha; Ejaz R. Parmar; Sumit Kumar Verma (Journal of Aquatic Food Product Technology, 2025)

Salicylic acid application mitigates plant oxidative stress by chelating with essential metals of soil - Abdul Basit Wani; Hemlata Chader; Abdul Haleem Wani; Sumit Kumar; Balram Jee; Afraim Koti; Niraj Upadhyay (Chemosphere, 2025)

Phytoremediation design based on field scale assessment of chromium uptake by crops and native plants in and around Rania-Khan Chandpur Cr-contaminated site, India - Nazia Afreen; Sumit Dhali; Pankaj Kumar Gupta; Vivek Kumar Nair; Sagar Dhanuskar; Vivek Dalvi; Vaibhav Deoli; Anushree Malik; Kamal Kishore Pant (Science of The Total Environment, 2025)

Uncovering deep trouble through multi-indices assessment: Geochemical fingerprints and human health risks of groundwater affected by coal mining - Sumit Kumar; Gourav Mondal; Vikas Sonkar; Shreya Chakraborty; Rupsha Nandi; Riddhi Basu; Debatri Dewanjee; Pankaj Kumar Roy; Pradip Bhattacharyya (Process Safety and Environmental Protection, 2025)

Mapping of flood inundated areas using earth observation data and cloud computing platform - Mohit Arora; Raj Setia; Randhir Singh; Sudhir Kumar Singh; Sumit Kumar; Brijendra Pateriya (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Prediction of thunderstorm evolution using deep learning models with doppler weather radar observations over southern part of India - Dharmadas Jash; Sumit Kumar; Arka Roy; E.A. Resmi; R.K. Sumesh; C.K. Unnikrishnan; Nita Sukumar (Dynamics of Atmospheres and Oceans, 2025)

UV-regenerable PVDF/PEI/SnO2 nano-composite membrane for antibiotic removal - Dharmveer Yadav; Triparna Chakraborty; Lokesh Kumar Sahu; Neha Redkar; Sumit Saxena; Shobha Shukla (Chemical Engineering Journal, 2025)

Study of Bay of Bengal cyclones for year 2023 using SCAT-3 and GFS datasets and numerical simulation of associated surges using SWAN + ADCIRC model - Ritama Das; Sumit Mondal; Anup Kumar Mandal; Neeru Jaiswal; Tushar Kanti Saha; Tarun Kumar De (Ocean Dynamics, 2025)

Investigating Root-Tuberization in Underutilized Legume Psophocarpus tetragonolobus (L.) DC. and Revealing the Role of Calcium-Dependent Protein Kinase in this Process - Rayees Ahmad Lone; Nasreen Bano; Shafquat Fakhrah; Umesh Chandra Sahoo; Shahre Aalam; Sumit Kumar Bag; Rojalin Pattanayak; Chandra Sekhar Mohanty (Journal of Plant Growth Regulation, 2025)

Comprehensive Evaluation of Potentially Toxic Elements in Tea: Bioavailability, Bio-accessibility, and Health Risk Analysis Using Multimodal Statistics - Riddhi Basu; Saibal Ghosh; Gourav Mondal; Sonali Banerjee; Shreya Chakraborty; Sumit Kumar; Pradip Bhattacharyya (Biological Trace Element Research, 2025)

Enhancing mycophytoremediation potential of Chrysopogon zizanioides in chromite-asbestos mine waste soil using arbuscular mycorrhizal fungi: A natural bioaccelerator for soil ecosystem rehabilitation - Sonali Banerjee; Saibal Ghosh; Sonam Jha; Sumit Kumar; Dibyendu Sarkar; Rupali Datta; Pradip Bhattacharyya (Science of The Total Environment, 2025)

Paleo-productivity reconstruction in Bay of Bengal during the past 1.3 Ma: Implications for glacial-interglacial dynamics and southern hemispheric processes - Barnita Banerjee; Monalisa Mallick; Vikash Kumar; E.V.S.S.K. Babu; Ozelim Luan; G. Balu; T. Vijaya Kumar; Nihar Ranjan Kar; Tanveer Hassan; Manish Tiwari; Thamizharasan Sakthivel; Prosenjit Ghosh; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Physico-chemical characterization of atmospheric particles during two intense dust storms in the vicinity of Thar Desert - Mamta Devi; Sumit Kumar Mishra; Aravindakshan Jayakumar; Supreet Kaur; Vikas Goel; Vijayan Narayanasamy; Gounda Abdul Basheed; Kartika Pandey (Atmospheric Pollution Research, 2025)

Molecular Dissection of Constans (CO) Homologs and Their Regulatory Role in Floral Induction of Mango (Mangifera indica L.) - M. Muthukumar; Anju Bajpai; Kasim Khan; Yashi Bajpai; Sandeep Kumar; Sumit Kumar Soni; Laxmi; V. K. Singh; T. Damodaran (Applied Fruit Science, 2025)

Physico-chemical Dynamics and Incidence of Jelly Seed Disorder in Mangifera indica L. cv. ‘Dashehari’ with Lengthening of Harvesting Time - Rubeena Abbas; Sumit K. Soni; Dinesh Kumar; Abha Singh; Israr Ahmad (Applied Fruit Science, 2025)

Antimicrobial activity of ethnomedicinal plants used by indigenous tribes of Southern Rajasthan districts of India to treat gastrointestinal diseases - Acharya Balkrishna; Hemant Sharma; Sonam Verma; Sumit Kumar Singh; Vidhi Dobhal; Vedpriya Arya (Next Research, 2025)

Deciphering the genomic and physiological basis of pH dependent siderophore production in Enterobacter sp. DRP3 and mitigation of lead stress in rice seedlings - Kunal Kumar Saha; Subhrangshu Mandal; Anik Barman; Sumit Chatterjee; Narayan Chandra Mandal (Journal of Hazardous Materials, 2025)

Evaluating the impact of arbuscular mycorrhizal fungi on the phytoremediation potential of Vetiveria zizanioides and Saccharum spontaneum on coal mine waste, India - Sumit Kumar; Sonali Banerjee; Suvasri Dutta; Pankaj Kumar Roy; Pradip Bhattacharyya (Journal of Environmental Chemical Engineering, 2025)

Advances in CRISPR/Cas9-driven strategies for microbial production and optimization of sugar polyols for food applications: A review - Manoj Kumar; Sumit Totade; Kanika Sharma; Ajinath Dukare; K. Pandiyan; Sujata Saxena (Food Bioscience, 2025)

Impact of indoor plant-induced relative humidity on PM concentration in indoor urban environment - Supreet Kaur; Sumit Kumar Mishra; Vikas Goel; Mayank Kumar; Rishabh Singh; Mamta Devi; Harish Chandra; Vijayan Narayanasamy; S.P. Singh; Parag Sharma; Prashant Kumar (Atmospheric Pollution Research, 2025)

Suitable Planting Material with Integrated Nutrient Management Can Enhance Productivity, Nutrient Use Efficiency and Profitability of Sugarcane - Sumit Sow; Navnit Kumar; Lalita Rana; A. K. Singh; Vipin Kumar; Harendra Singh; Kavita; Shailesh Kumar (Journal of Soil Science and Plant Nutrition, 2025)

Biotic Stress Alleviation in Plant Using Rhizobacteria: An Overview of Mechanism of Action, Antimicrobial Compounds Production, (Nano) Formulations and Employment Methods - Anuj Rana; Annu Rani; KR. Nayana; Sumit Deswal; Arvind Pratap Singh; Sravendra Rana; Madhvi Chahar; Namita Singh; Rahul Kumar Dhaka (Indian Journal of Microbiology, 2025)

A novel approach to analyzing the 3D slope of Mount St. Helens via soft computing techniques - Sumit Kumar; Divesh Ranjan Kumar; Manish Kumar; Warit Wipulanusat; Manop Kaewmoracharoen (Earth Science Informatics, 2025)

Soil Attributes Modulate the Fungal Population and Diversity of Phytopathogens and Biocontrol Agents - Isha Verma; Sumit K. Soni; Rahul Kumar; Bhavya Priyadarshini Mishra; Udit Yadav; Anshu anshu; Touseef Fatima; Sanjeeva Nayaka; Mariya Naseem; Suchi Srivastava; Poonam C. Singh (Agricultural Research, 2025)

Development of new spectral indices for mapping of crop residue burning using satellite remote sensing - Sumit Kumar; Sanjay Kumar Ghosh; Brijendra Pateriya (International Journal of Remote Sensing, 2025)

Development of a NIRS-based prediction model for measurement of whole wheat flour arabinoxylan content to aid rapid germplasm screening - Adithya P. Balakrishnan; Antil Jain; Sumit Kr Singh; Arvind Kumar Ahlawat; Jai Prakash Jaiswal; Anju Mahendru-Singh; Rakesh Bhardwaj (Journal of Cereal Science, 2025)

Investigating the possibility of using waste plastic fuel and gasoline fuel mixture in gasoline direct injection engine through experimental studies and the Taguchi method - Sumit Kanchan; Abhishek Mukhija; Subhash Sharma; Rohitash Choudhary; Rajesh Choudhary; Ravinder Kumar (Fuel, 2025)

A Multifaceted Approach Assessing Heavy Metal Contamination and Health Risk in Tea Garden Soils: Insight Through Hot-Spot Analysis and Machine Learning Techniques - Riddhi Basu; Sonali Banerjee; Saibal Ghosh; Gourav Mondal; Sumit Kumar; Jajati Mandal; Pradip Bhattacharyya (Water, Air, & Soil Pollution, 2025)

Functionalized triptycene-based porous polymer networks for pharmaceuticals removal: Unveiling role of ultrasound in adsorption - Sumit Kumar; Arkaprabha Giri; G. Shreeraj; Abhijit Patra; Ligy Philip (Journal of Environmental Chemical Engineering, 2025)

Microphysical characteristics of shallow precipitating systems in the southwest monsoon season: An analysis using in-situ and remote sensing observations - Anusha Andrews; R.K. Sumesh; E.A. Resmi; Nita Sukumar; Gadha Gopan; Lekshmi Anilkumar; Sumit Kumar; M.G. Manoj; Dharmadas Jash; C.K. Unnikrishnan (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Assessment of Surface PM2.5 Concentrations over India using Modern-Era Retrospective Analysis for Research and Applications, Version 2 (MERRA-2) Reanalysis Data - Sumit Singh; Amarendra Singh; Atul Kumar Srivastava; Virendra Pathak; Ajay Kumar; Vivek Singh (Pure and Applied Geophysics, 2025)

Preparation and Evaluation of N-Acetyl D-Glucosamine Ethosomal Gel for the Treatment of Hyperpigmentation - Umair Khan; Prashant Kumar; Sabina Yasmin; Sumit Durgapal; Sumel Ashique; Anurag Verma; Mohammad Yousuf Ansari (Journal of Pharmaceutical Innovation, 2025)

The interplay of p16INK4a and non-coding RNAs: bridging cellular senescence, aging, and cancer - Ashok Kumar Balaraman; Muhammad Afzal; Ehssan Moglad; M. Arockia Babu; G. Padma Priya; Pooja Bansal; Sumit Rajotiya; Benod Kumar Kondapavuluri; Imran Kazmi; Sami I. Alzarea; Kavita Goyal; Haider Ali (Biogerontology, 2025)

Response of Bioformulations and Inorganic Fertilizers for Productivity, Quality, and Soil Microbial Activity of Banana in the Subtropics - Dinesh Kumar; Govind Kumar; K. K. Srivastava; Vinod Kumar Singh; Sumit K. Soni (Applied Fruit Science, 2025)

Identifying the causal agent of floral malformation as Fusarium complex using metagenomic and metabolomic approaches - M. Muthukumar; Anju Bajpai; Sumit K. Soni; Sanjay Kumar Singh; Yashi Bajpai; Sandeep Kumar; Laxmi (Physiological and Molecular Plant Pathology, 2025)

Determination of beneficial effects of cuminaldehyde on hyperglycemia associated kidney malfunctions - Abhishek Kumar Das; Sumit Ghosh; Parames C. Sil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Extracellular Proteins of Pseudomonas bubulae KU04 as a Resource for Potent Antimicrobial Peptides Against Acinetobacter Baumannii and Pseudomonas aeruginosa - Rajendra Kr Roy; Raju Biswas; Rajdeep Shaw; Sumit Kumar Hira; Rajib Bandopadhyay (International Journal of Peptide Research and Therapeutics, 2025)

Impact of polysaccharide addition on the technological aspects of low lactose milk powders - Chandrakanta Sen; Sumit Arora; Richa Singh; Vivek Sharma; Ganga Sahay Meena; Ashish Kumar Singh (Food Research International, 2025)

Anti-adipogenic and anti-steatotic potential of edible pigment bixin and annatto seed extracts: LC-MS based bioactive profiling and in vitro biochemical validation - Sonakshi Puri; Sumit Kumar Mandal; Tripti Joshi; Nikita; Ayush Srivastava; Pankaj Kumar Sharma; P.R. Deepa (Food Bioscience, 2025)

Next-Generation heavy metal water Treatment: A Primer on modified Capacitive deionization - Aditya Tripathi; Sumit Dahiya; Brijesh Kumar Mishra (Chemical Engineering Journal, 2025)

Trash Amended with Trichoderma Effects on Cane Yield, Soil Carbon Dynamics, and Enzymatic Activities under Plant–Ratoon System of Sugarcane in Calcareous Soil - Navnit Kumar; Sumit Sow; Lalita Rana; Shivani Ranjan; A. K. Singh (Sugar Tech, 2025)

Performance assessment of solar PV panels under varying environmental conditions: a laboratory and field-based approach for sustainable energy in mining operations - Abhishek Kumar Tripathi; Mangalpady Aruna; Sumit Sharma; Chandan Kumar; Mukesh Didwania (Environmental Science and Pollution Research, 2025)

The interplay of senescence and MMPs in myocardial infarction: implications for cardiac aging and therapeutics - Ashok Kumar Balaraman; Abdulmalik Saleh Alfawaz Altamimi; M. Arockia Babu; Kavita Goyal; G. PadmaPriya; Pooja Bansal; Sumit Rajotiya; M. Ravi Kumar; Pranchal Rajput; Mohd Imran; Gaurav Gupta; Lakshmi Thangavelu (Biogerontology, 2025)

New Report of Eulecanium Tiliae L. Infestation in Apple Orchards of the Western Himalayan Cold Desert: Morphological and Molecular Insights - Sumit Vashisth; Sunil Joshi; Sawraj Jit Singh; Pankaj Kumar; Madhurjit Singh Rathore; Sudhir Verma (Applied Fruit Science, 2025)

Mapping crop water productivity of rice across diverse irrigation and fertilizer rates using field experiment and UAV-based multispectral data - Sumit Kumar Vishwakarma; Benu Bhattarai; Kritika Kothari; Ashish Pandey (Remote Sensing Applications: Society and Environment, 2025)

Understanding behaviour and performance of flow electrode capacitive deionization (FCDI) during simultaneous selective removal of Chromium (Cr (VI)) and Fluoride from brackish wastewater - Sumit Dahiya; Aakansha Singh; Aditya Tripathi; Brijesh Kumar Mishra (Journal of Water Process Engineering, 2025)

In silico design and assessment of a multi-epitope peptide vaccine against multidrug-resistant Acinetobacter baumannii - Shiv Nandan Sah; Sumit Gupta; Neha Bhardwaj; Lalit Kumar Gautam; Neena Capalash; Prince Sharma (In Silico Pharmacology, 2024)

Flash flood dynamics in the foothills of the NW Himalayas: insights into hydrological and morphological controls - Sumit Sagwal; Sandeep Panda; Dipanwita Sengupta; Mohd Shahrukh; Sohan Kumar; Anil Kumar; Som Dutt (Environmental Monitoring and Assessment, 2024)

Silencing Nrf2 in cisplatin resistant non-small cell lung cancer cells augments sensitivity towards EGFR inhibitor - Chandrani Fouzder; Alpana Mukhuty; Dipanjan Chattopadhyay; Snehasis Das; Sumit Kumar Hira; Rakesh Kundu (Toxicology in Vitro, 2024)

In search of poly-3-hydroxybutyrate (PHB): A comprehensive review unveiling applications and progress in fostering a sustainable bio-circular economy - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Krishnendu Mondal; Ashish Kumar Singh; Sonia Tamang; Palash Hazra; Nagendra Thakur; Rajendra Bhanwaria; Sumit G Gandhi; Vinod Kumar (Food and Bioproducts Processing, 2024)

Multi-omics analysis reveals the positive impact of differential chloroplast activity during in vitro regeneration of barley - Parul Sirohi; Chanderkant Chaudhary; Mayank Sharma; Ravi Bodampalli Anjanappa; Suchi Baliyan; Ritika Vishnoi; Sumit Kumar Mishra; Reeku Chaudhary; Bhairavnath Waghmode; Anuj Kumar Poonia; Hugo Germain; Debabrata Sircar; et al. (Plant Molecular Biology, 2024)

Luteibacter sahnii sp. nov., A Novel Yellow-Colored Xanthomonadin Pigment Producing Probiotic Bacterium from Healthy Rice Seed Microbiome - Gagandeep Jaiswal; Rekha Rana; Praveen Kumar Nayak; Rekha Chouhan; Sumit G. Gandhi; Hitendra K. Patel; Prabhu B. Patil (Current Microbiology, 2024)

Utilization of publicly available data to summarize spatio‐temporal patterns of fish health events of Atlantic salmon ( Salmo salar ) reported by marine finfish industries in British Columbia ( BC ), Canada - Sumit Jyoti; Beibei Jia; Sonja Saksida; Henrik Stryhn; Derek Price; Krishna Kumar Thakur (Journal of Fish Diseases, 2024)
Atlantic salmon aquaculture companies in British Columbia (BC) must report fish health events to Fisheries and Oceans Canada (DFO) as part of their licensing conditions. Our study aimed to summarize these fish health events reported by Atlantic salmon sites in BC to identify spatial and spatio‐temporal clusters. We conducted descriptive, retrospective global, and local cluster analyses using Moran's I and scan statistics. Between 2016 and 2022, 265 fish health events were reported. The annual incidence ranged from 5.60 (95% CI: 3.90–7.80) to 6.86 (95% CI: 4.70–9.60) health events per 100 active site‐months. The most common events were yellow mouth (60.75%; 161/265) and salmonid rickettsial septicaemia (SRS) (15.47%; 41/265). The Moran's I index was positive and significant for yellow mouth, SRS, and overall fish health events at different distance bands. Most of the spatial and spatio‐temporal clusters were identified in the west‐central and southwestern parts of Vancouver Island. Our study hypothesizes that management practices, environmental conditions, and water quality parameters may have influenced the increased reporting of fish health events in these regions. Overall, the study highlights the potential of publicly available data for practical risk mapping in understanding the patterns of farmed Atlantic salmon diseases in BC.

Hesperidin’s role in the treatment of lung cancer: In-silico and In-vitro findings - Swati Arora; Sumit Sheoran; Bhuvanesh Baniya; Naidu Subbarao; Himanshu Singh; Dhamodharan Prabhu; Neeraj Kumar; Smita C. Pawar; Sugunakar Vuree (In Silico Pharmacology, 2024)

CB[6]/ZnO chelated superoleophobic-hydrophilic PVDF membranes for one-step remediation of multi-contaminant in wastewater - Triparna Chakraborty; Dharmveer Yadav; Lokesh Kumar Sahu; Manoj Kumar Pandey; Sumit Saxena; Shobha Shukla (Chemosphere, 2024)

Developing offshore renewable energy systems in Australia: Existing regulatory challenges and requirements for reliability assurance - Mohammad Mahdi Abaei; Sumit Kumar; Ehsan Arzaghi; Nima Golestani; Nagi Abdussamie; Vikram Garaniya; Fatemeh Salehi; Mohsen Asadnia; Tina Soliman Hunter; Alexandre Pichard; Rouzbeh Abbassi (Ocean & Coastal Management, 2024)

Intensification mechanisms and moisture dynamics of super cyclonic storm ‘Amphan’ over the Bay of Bengal: Implications for aerosol re-distribution - Vivek Singh; Atul Kumar Srivastava; Anu Gupta; Rakesh Teja Konduru; Amarendra Singh; Sumit Singh; Arun Kumar; Deewan Singh Bisht; Abhay Kumar Singh (Science of The Total Environment, 2024)

Ecohydrological and hydrogeological dynamics of groundwater springs in Eastern Himalaya, India - Manish Kumar; Sumit Sen; Himanshu Kulkarni; Shrinivas Badiger; Girish R. Varma; Jagdish Krishnaswamy (Groundwater for Sustainable Development, 2024)

Hydrogen peroxide mediated thermo-catalytic conversion of carbon dioxide to C1-C2 products over Cu (0) - Vishrant Kumar; Nicky Kumar Lamba; Aamir Baig; Amit Kumar Sonker; Nikhil Sharma; Jaidev Kaushik; Kumud Malika Tripathi; Sonal; Sumit Kumar Sonkar (Chemical Engineering Journal, 2024)

Tree species diversity and population dynamics and regeneration status in the tropical forest of Tripura: confluence of indo-burmese biodiversity hotspot - Amal Debnath; Saptadip Majumder; Bipul Das Chowdhury; Alekhya Sarkar; Sumit Kumar Das; Bimal Debnath (Vegetos, 2024)

Involvement of Sirt1-FoxO3a-Bnip3 axis and autophagy mediated mitochondrial turnover in according protection to hyperglycemic NRK-52E cells by Berberine - Sugandh Saxena; Sumit Kumar Anand; Ankita Sharma; Poonam Kakkar (Toxicology in Vitro, 2024)

Inter-seasonal variation of rainfall microphysics as observed over New Delhi, India - Mohit Kumar; Kaustav Chakravarty; Sachin Deshpande; Sumit Kumar; Atul Srivastava (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Crustal origin for olivine in the lunar Shioli crater ejecta boulders: Insights from the geological setting of Theophilus crater and Nectaris basin - P. Senthil Kumar; Abhisek Mishra; Vivek Krishnan; Netra S. Pillai; Sumit Pathak; Sriram S. Bhiravarasu; Shyama Narendranath; K. Jaya Prasanna Lakshmi; Satadru Bhattacharya (Icarus, 2024)

Hydrometeor categorization in stratiform and convective precipitation systems over a tropical coastal region - Sumit Kumar; Dharmadas Jash; E. A. Resmi; R. K. Sumesh; Gadha Gopan; Mohit Kumar; Anusha Andrews; Nita Sukumar (Theoretical and Applied Climatology, 2024)

Wet and dry spell induced changes in the soil CO2 effluxes of Pine and Oak ecosystems of Central Himalaya: a comparative assessment for monsoon and winter seasons - Sandipan Mukherjee; Priyanka Lohani; Srabanti Ballav; Pooja Mehta; K. Chandra Sekar; Sumit Pundir; Kireet Kumar; Surendra Pratap Singh (Environmental Monitoring and Assessment, 2024)

Experimental and numerical investigation on the hydroelastic response of barge and KVLCC2 ship - Binyang Xie; Guanghua He; Chuankai Zhao; Penglin Jing; Sumit Kumar Pal; Kazuhiro Iijima; Ruijia Jin; Bangqi Chen; Hassan Ghassemi (Ocean Engineering, 2024)

Characterization and utilization of algal and wheat husk biochar as biofertilizers for sustainable soil amelioration - Sharma Mona; Neha Saini; Sujata; Sumit Kumar; Anuj Sharma; Anjali Yadav; Navita Yadav; Bansal Deepak (Bioresource Technology Reports, 2024)

Effect of Methyl Jasmonate and Salicylic Acid on the Enrichment of Carbazole Alkaloids in Murraya koenigii (L.) Spreng - Sumit Kumar Singh; Gaurav Sharma; Pratibha Singh; Sanjeev K. Shukla; Sanjeev Kanojiya; Dipak Kumar Mishra (Journal of Plant Growth Regulation, 2024)

A Novel Rhodamine Probe Acting as Chemosensor for Selective Recognition of Cu2+ and Hg2+ Ions: An Experimental and First Principle Studies - Pawan Kumar Sada; Amit Bar; Amanpreet Kaur Jassal; Prabhat Kumar; S. Srikrishna; Alok Kumar Singh; Sumit Kumar; Laxman Singh; Abhishek Rai (Journal of Fluorescence, 2024)

Self- and semi-supervised learning for evacuation time modeling within fire emergencies in nuclear power plants - Geonhui Jang; Sumit Kumar Singh; Saerin Lim; Jinsoo Bae; Jongkook Heo; Yu Zhang; Weon Gyu Shin; Seoung Bum Kim (Process Safety and Environmental Protection, 2024)

The emergence of digitalization to the manufacturing sector in the sustainability context: A multi-stakeholder perspective analysis - M.S. Kiran Sankar; Sumit Gupta; Sunil Luthra; Sandeep Jagtap; Sanjeet Singh; Anil Kumar (Journal of Cleaner Production, 2024)

Development of characteristic equations of conical solar still by incorporating N identical concentrator collectors with/without photovoltaic panel: A comparative investigation - Nandan Kumar; Danduprolu Purnachandrakumar; Abhishek Saxena; Sumit Tiwari; Desh Bandhu Singh; Harender Sinhmar (Desalination, 2024)

Unraveling the enigma of root-knot nematodes: from origins to advanced management strategies in agriculture - Sumit Vashisth; Pankaj Kumar; Vishav Gaurav Singh Chandel; Rakesh Kumar; Subhash Chander Verma; Rajeshwar Singh Chandel (Planta, 2024)

Guggulsterone Selectively Modulates STAT-3, mTOR, and PPAR-Gamma Signaling in a Methylmercury-Exposed Experimental Neurotoxicity: Evidence from CSF, Blood Plasma, and Brain Samples - Sumit Kumar; Sidharth Mehan; Zuber Khan; Ghanshyam Das Gupta; Acharan S. Narula (Molecular Neurobiology, 2024)

Unsteady two-dimensional distribution of suspended sediment transport in open channels - Arun Kumar; Sumit Sen; Sourav Hossain; Koeli Ghoshal (Environmental Fluid Mechanics, 2024)

The Emerging Role of Natural Products in Cancer Treatment - Sumit Ghosh; Sanjib Kumar Das; Krishnendu Sinha; Biswatosh Ghosh; Koushik Sen; Nabanita Ghosh; Parames C. Sil (Archives of Toxicology, 2024)

Jelly Seed Disorder in Mango: A Comprehensive Review of Current Status and Future Directions - Sharad Kumar Dwivedi; Dushyant Mishra; Alok Kumar Gupta; Vishambhar Dayal; Dinesh Kumar; Sanjay Kumar Singh; P. L. Saroj; Sumit K. Soni (Applied Fruit Science, 2024)

Heavy metals and trace minerals in commonly available shark species from North East Arabian Sea: A human health risk perspective - Ashish Kumar Jha; Pankaj Kishore; Shunmugavel Chinnadurai; Sumit Kumar Verma; Rajan Kumar; S. Sreejith; K. Sarika (Environmental Research, 2024)

Heat-stress-responsive HvHSFA2e gene regulates the heat and drought tolerance in barley through modulation of phytohormone and secondary metabolic pathways - Sumit Kumar Mishra; Chanderkant Chaudhary; Suchi Baliyan; Anuj Kumar Poonia; Parul Sirohi; Meenakshi Kanwar; Snehi Gazal; Annu Kumari; Debabrata Sircar; Hugo Germain; Harsh Chauhan (Plant Cell Reports, 2024)

Trehalose Promotes Clearance of Proteotoxic Aggregation of Neurodegenerative Disease-Associated Aberrant Proteins - Prashant Kumar; Sumit Kinger; Ankur Rakesh Dubey; Yuvraj Anandrao Jagtap; Akash Choudhary; Amit Prasad; Hem Chandra Jha; Rohan Dhiman; Ravi Kumar Gutti; Amit Mishra (Molecular Neurobiology, 2024)

Composition of heavy metals in sediment, water, and fish of the Ganga and Yamuna Rivers in two major cities of India - Sumit Kumar; Amita Saxena; Rajeev Kumar Srivastava; Suraj Bhan Singh; Raj Narayan Ram; Parvaiz Ahmad Ganie; Ravindra Posti; Nityanand Pandey (Environmental Monitoring and Assessment, 2024)

From waste management to circular economy: Leveraging thermophiles for sustainable growth and global resource optimization - Ishfaq Nabi Najar; Prayatna Sharma; Rohit Das; Sonia Tamang; Krishnendu Mondal; Nagendra Thakur; Sumit G. Gandhi; Vinod Kumar (Journal of Environmental Management, 2024)

PVDF-Halloysite-Ceria multifunctional membrane for one-step treatment to industrial effluent - Triparna Chakraborty; Dharmveer Yadav; Amita Bedar; Manoj Kumar Pandey; Sumit Saxena; Shobha Shukla (Journal of Environmental Chemical Engineering, 2024)

Targeting lipid-sensing nuclear receptors PPAR (α, γ, β/δ): HTVS and molecular docking/dynamics analysis of pharmacological ligands as potential pan-PPAR agonists - Sumit Kumar Mandal; Sonakshi Puri; Banoth Karan Kumar; Mohammed Muzaffar-Ur-Rehman; Pankaj Kumar Sharma; Murugesan Sankaranarayanan; P. R. Deepa (Molecular Diversity, 2024)

Sustainability Assessment of High-Value Vegetable Crops Using Biopriming Approach Towards Improved Performance, Nutritional Security, and Smallholder Farmers - Sumit Kumar Tripathi; Jayesh Singh; Amitava Rakshit (Journal of Soil Science and Plant Nutrition, 2024)

Tailored midgut gene expression in Spodoptera litura (Lepidoptera: Noctuidae) feeding on Zea mays indicates a tug of war - Archana Singh; Sumit Kumar; Manisha Yadav; Megha Kumari; Indrakant K. Singh (Arthropod-Plant Interactions, 2024)

Revitalization of Overcrowded and Unproductive Mango (Mangifera indica L. cv ‘Dashehari’) Orchard Through Better Light Interception via Canopy Management - K. K. Srivastava; Dinesh Kumar; S. K. Dwivedi; Sumit K. Soni; S. R. Singh; S. K. Shukla (Applied Fruit Science, 2024)

U–Pb zircon geochronology of the Proterozoic siliciclastic stratal succession of the Kumaun Lesser Himalaya: Implications for regional stratigraphic correlation - Poonam Jalal; Sumit K Ghosh; Mohit Puniya; Gajender Kumar (Journal of Earth System Science, 2024)

A risk-based multi-criteria decision-making framework for offshore green hydrogen system developments: Pathways for utilizing existing and new infrastructure - Sumit Kumar; Ehsan Arzaghi; Til Baalisampang; Mohammad Mahdi Abaei; Vikram Garaniya; Rouzbeh Abbassi (Sustainable Production and Consumption, 2024)

Revealing soil microbial ecophysiological indicators in acidic environments laden with heavy metals via predictive modeling: Understanding the impacts of black diamond excavation - Sumit Kumar; Shreya Chakraborty; Saibal Ghosh; Sonali Banerjee; Gourav Mondal; Pankaj Kumar Roy; Pradip Bhattacharyya (Science of The Total Environment, 2024)

Reduction of maillard browning in spray dried low-lactose milk powders due to protein polysaccharide interactions - Chandrakanta Sen; Sumit Arora; Richa Singh; Vivek Sharma; Ganga Sahay Meena; Ashish Kumar Singh (Food Research International, 2024)

A simulacrum of proliferative vitreoretinopathy (PVR): development and proteomics-based validation of an in vitro model - Sumit Sharma; Amit Kumar Thakur; Maryada Sharma; Deeksha Katoch; Reema Bansal; Ramandeep Singh; Mangat R. Dogra; Manni Luthra-Guptasarma (Journal of Proteins and Proteomics, 2024)

Severity of Agricultural Injuries and Its Economic Consequences in Border Belt of Gurdaspur District of Punjab, India - Sumit Chopra; Pramod Kumar; Manoj Kumar (Journal of Agromedicine, 2024)

Field-scale assessment of soil, water, plant, and soil microbiome in and around Rania-Khan Chandpur Chromium contaminated site, India - Pankaj Kumar Gupta; Vivek Kumar Nair; Vivek Dalvi; Sumit Dhali; Anushree Malik; Kamal Kishore Pant (Journal of Hazardous Materials, 2024)

Unveiling the molecular mechanisms of arsenic tolerance and resilience in the primitive bryophyte Marchantia polymorpha L. - Prasanna Dutta; Priti Prasad; Yuvraj Indoilya; Neelam Gautam; Amit Kumar; Vinay Sahu; Monica Kumari; Shivani Singh; Ashish Kumar Asthana; Sumit Kumar Bag; Debasis Chakrabarty (Environmental Pollution, 2024)

Assessment of terminal heat tolerance ability of wheat genotypes based on chemometric analysis and agro-physiological traits - S. K. Dwivedi; Sumit K. Soni; J. S. Mishra; T. K. Koley; Santosh Kumar (Acta Physiologiae Plantarum, 2024)

Semecarpus anacardium L.f. leaf extract exhibits activities against breast cancer and prolongs the survival of tumor-bearing mice - Rajesh Kumar Singh; Bhagaban Mallik; Amit Ranjan; Ruchita Tripathi; Sumit Singh Verma; Vinamra Sharma; Subash Chandra Gupta; Anil Kumar Singh (Natural Product Research, 2024)

Comparative evaluation of management modules against Maydis leaf blight disease in maize (Zea mays) - Sumit Kumar Aggarwal; K. S. Hooda; Harleen Kaur; Robin Gogoi; Prashant Chauhan; P. K. Bagaria; Pardeep Kumar; Mukesh Choudhary; Rahul Kumar Tiwari; Milan Kumar Lal (European Journal of Plant Pathology, 2024)

Enhancement of nutritional quality in maize grain through QTL-based approach - Pardeep Kumar; Ningthai Longmei; Mukesh Choudhary; Mamta Gupta; Bhupender Kumar; B. S. Jat; Bharat Bhushan; Manesh Chander Dagla; Sumit Kumar Aggarwal (Cereal Research Communications, 2024)

Elucidating the synergistic effect of acidity and metalloid poisoning on the microbiome through metagenomics and machine learning approaches - Shreya Chakraborty; Saibal Ghosh; Sonali Banerjee; Sumit Kumar; Pradip Bhattacharyya (Environmental Research, 2024)

Optimization and characterization of hybrid bio-briquettes produced from the mixture of sawdust, sugarcane bagasse, and paddy straw - Arshad Ali; Deepak Chhabra; Meena Kumari; Manisha; Pinkey; Sumit Tiwari; Ravinder Kumar Sahdev (Environmental Science and Pollution Research, 2024)

Photovoltaic-wind-battery and diesel generator-based hybrid energy system for residential buildings in smart city Coimbatore - Santhana Krishnan Thirumalai; Alagar Karthick; Pradyumna Kumar Dhal; Sumit Pundir (Environmental Science and Pollution Research, 2024)

Insight into the Biomass-Based Briquette Generation from Agro-Residues: Challenges, Perspectives, and Innovations - Arshad Ali; Meena Kumari; Manisha; Sumit Tiwari; Mahesh Kumar; Deepak Chhabra; Ravinder Kumar Sahdev (BioEnergy Research, 2024)

Nonlocal effect on shear wave propagation in a fiber-reinforced poroelastic layered structure subjected to interfacial impulsive disturbance - Rachaita Dutta; Soumik Das; Neelima Bhengra; Sumit Kumar Vishwakarma; Sandip Kumar Das (Soil Dynamics and Earthquake Engineering, 2024)

Bibliometric analysis, physical properties, and experimental evaluation of additives-diesel ternary blends - Chandan Kumar; Mukesh Kumar; Umesh Kumar Das; Sumit Sharma (Environmental Science and Pollution Research, 2023)

Can graphene-based composites and membranes solve current water purification challenges - a comprehensive review - Chetna Tewari; Gaurav Tatrari; Sumit Kumar; Mayank Pathak; Kundan Singh Rawat; Young Nam Kim; Biswajit Saha; Yong Chae Jung; Prithu Mukhopadhyay; Nanda Gopal Sahoo (Desalination, 2023)

Utilization of steel industry waste derived magnetic iron-oxide nanoparticles for reverse water gas shift reaction - Vishrant Kumar; Nicky Kumar Lamba; Aamir Baig; Jaidev Kaushik; Tushit Jha; Sonal; Sumit Kumar Sonkar (Chemical Engineering Journal, 2023)

Nutraceutical and flavor profiles in underutilized desert legumes of India: gene editing strategies towards sustainable food development - Tripti Joshi; Hansa Sehgal; Sumit Kumar Mandal; Mukul Joshi; P. R. Deepa; Pankaj Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2023)

The distribution and characterisation of microplastics in air, surface water and sediment within a major river system - Imogen E. Napper; Anju Baroth; Aaron C. Barrett; Sunanda Bhola; Gawsia W. Chowdhury; Bede F.R. Davies; Emily M. Duncan; Sumit Kumar; Sarah E. Nelms; Md. Nazmul Hasan Niloy; Bushra Nishat; Taylor Maddalene; et al. (Science of The Total Environment, 2023)

Carbon offset potential of biochar based straw management under rice- wheat system along Indo-Gangetic Plains of India - Shivvendra Singh; Sumit Chaturvedi; Prayasi Nayak; Vipin Chandra Dhyani; Tony Manoj K. Nandipamu; Dhananjay Kumar Singh; Pratibha Gudapaty; Prabhakar Mathyam; Kanchu Srinivasrao; Kasivelu Govindaraju (Science of The Total Environment, 2023)

Analysing role of airborne particulate matter in abetting SARS-CoV-2 outbreak for scheming regional pandemic regulatory modalities - Pradeep Bhadola; Vishal Chaudhary; Kalaimani Markandan; Rishi Kumar Talreja; Sumit Aggarwal; Kuldeep Nigam; Mohammad Tahir; Ajeet Kaushik; Sarvesh Rustagi; Mohammad Khalid (Environmental Research, 2023)

A Web-Enabled Tool for Site Suitability Mapping for Managed Aquifer Recharge (MAR) Using Google Earth Engine (GEE) and Multi-Criteria Decision Analysis (MCDA) - Nitesh Patidar; Basant Yadav; Sumit Kumar; Abhay Raj; Gopal Krishan; Surjeet Singh; Bhaskar Jyoti Deka; Sanghyun Jeong; Ashish Pandey; Yutaka Matsuno; R. D. Singh (Water Resources Management, 2023)

Unraveling the terpene synthase family and characterization of BsTPS2 contributing to (S)-( +)-linalool biosynthesis in Boswellia - Pravesh Bhargav; Seema Chaurasia; Aashish Kumar; Gaurav Srivastava; Yatish Pant; Chandan Singh Chanotiya; Sumit Ghosh (Plant Molecular Biology, 2023)

Identifying the tectonically induced mineralisation zone in the central part of Dharwar-Shimoga greenstone belt, Western Dharwar Craton: an integrated analysis of gravity and magnetic data - Niharika Das; Sumit Kumar Bhattacharya; Satya Narayan; D. Livingston (Acta Geophysica, 2023)

Two new and seven known species of the genus Belondira Thorne, 1939 (Dorylaimida: Belondiroidea) from Western Ghats of India - Sumit Kumar; Wasim Ahmad (Biologia, 2023)

The Flower Colour Influences Spontaneous Nectaring in Butterflies: a Case Study with Twenty Subtropical Butterflies - Sumit Kumar Sinha; Avishek Dolai; Arjan Basu Roy; Sourav Manna; Amlan Das (Neotropical Entomology, 2023)

Techno-economic assessment of doxycycline recovery using rice straw biochar: A circular economic execution - Kasturi Poddar; Debapriya Sarkar; Jyotsna Rani Sahu; Pritam Bajirao Patil; Sumit Kumar Pal; Angana Sarkar (Chemosphere, 2023)

Targeting lipid metabolism in plants for non-animal sources of nutraceuticals towards sustainable food production and scale up - Sonakshi Puri; Sumit Kumar Mandal; Akriti Srivastava; Ishita Agrawal; P.R. Deepa (Food Bioscience, 2023)

Hydrometeorological field instrumentation in Lesser Himalaya to advance research for future water and food security - Vikram Kumar; Sumit Sen (Environmental Monitoring and Assessment, 2023)

Comparative transcriptomic analysis of the chickpea glutaredoxin (CaGrx) gene over-expressed in Arabidopsis thaliana is associated with drought tolerance by modulating the plant defense system - Anil Kumar; Nasreen Bano; Mohd Akram Ansari; Varun Kumar; Sumit K. Bag; Indraneel Sanyal (Acta Physiologiae Plantarum, 2023)

A non-destructive approach to develop tree-level allometric equations for estimating aboveground biomass in the forests of Tripura, Northeast India - Abhilash Dutta Roy; Sumit Kumar Das; Bimal Debnath (Tropical Ecology, 2023)

Recent developments on photovoltaic thermal drying systems: a clean energy production - Manisha; Sumit Tiwari; Deepak Chhabra; Meena Kumari; Prabhakar Tiwari; Ravinder Kumar Sahdev (Clean Technologies and Environmental Policy, 2023)

Dynamic impedance parameters of floating piles subjected to coupled harmonic vibration - Deepthi Sudhi; Sumit Kumar Sinha; Sanjit Biswas; Bappaditya Manna (Arabian Journal of Geosciences, 2023)

Arid/semi-arid flora as a treasure trove of bioactives and bioenergy: the case for underutilized desert legumes towards environmental sustainability - Tripti Joshi; Sumit Kumar Mandal; Vidushi Asati; Perinkulam Ravi Deepa; Pankaj Kumar Sharma (Environmental Science and Pollution Research, 2023)

Rottlerin renders a selective and highly potent CYP2C8 inhibition to impede EET formation for implication in cancer therapy - Diksha Manhas; Shipra Bhatt; Garima Rai; Vinay Kumar; Sahil Bharti; Sumit Dhiman; Shreyans K. Jain; Deepak K. Sharma; Probir Kumar Ojha; Sumit G. Gandhi; Anindya Goswami; Utpal Nandi (Chemico-Biological Interactions, 2023)

In silico screening, synthesis, characterization and biological evaluation of novel anticancer agents as potential COX-2 inhibitors - Ankita Sahu; Dibyabhaba Pradhan; Babita Veer; Sumit Kumar; Ram Singh; Khalid Raza; Moshahid A. Rizvi; Arun Kumar Jain; Saurabh Verma (DARU Journal of Pharmaceutical Sciences, 2023)

Assessing pollution and health risks from chromite mine tailings contaminated soils in India by employing synergistic statistical approaches - Sonali Banerjee; Saibal Ghosh; Sonam Jha; Sumit Kumar; Gourav Mondal; Dibyendu Sarkar; Rupali Datta; Abhishek Mukherjee; Pradip Bhattacharyya (Science of The Total Environment, 2023)

Sol-gel auto-combustion developed Nd and Dy co-doped Mg nanoferrites for photocatalytic water treatment, electrocatalytic water splitting and biological applications - Gaurav Katoch; Jyoti Prakash; Rohit Jasrotia; Ankit Verma; Ritesh Verma; Swati Kumari; Tokeer Ahmad; Sachin Kumar Godara; Jahangeer Ahmed; Abhishek Kandwal; Mohd Fazil; Pradip K. Maji; et al. (Journal of Water Process Engineering, 2023)

OGF nanocomposite foam for enhanced recyclability and oil-recovery - Dharmveer Yadav; Rahul Kumar Das; Sumit Saxena; Shobha Shukla (Journal of Cleaner Production, 2023)

Fabrication, characterization and performance analysis of a two-step arsenic bio-filter column using Delftia spp. BAs29 and fired red mud pellets - Rimi Biswas; S. Rahul; Sumit Kumar Pal; Angana Sarkar (Environmental Geochemistry and Health, 2023)

Evaluation of pre-trained convolutional neural networks for the development of web/mobile-based bird species identification applications under Indian Bioresource Information Network (IBIN) framework - Sumit Kumar Chaudhary; Sameer Saran (Environmental Sustainability, 2023)

Sustainable Bifunctional ZnO Composites For Synchronous Adsorption And Reduction Of Cr(VI) to Cr(III) - Nurudeen Abiola Oladoja; Joseph Adebusola Ogunniyi; Eric TobechukwuAnthony; Sumit Kumar; Stephan Hofmann (Environmental Science and Pollution Research, 2023)

Insights into decision-making for offshore green hydrogen infrastructure developments - Sumit Kumar; Ehsan Arzaghi; Til Baalisampang; Vikram Garaniya; Rouzbeh Abbassi (Process Safety and Environmental Protection, 2023)

A global meta-analysis of toxic metals in continental surface water bodies - Amit Kumar; Vinod Kumar; Shevita Pandita; Sumit Singh; Renu Bhardwaj; Memet Varol; Jesus Rodrigo-Comino (Journal of Environmental Chemical Engineering, 2023)

Effect of different bagging materials on guava fruit physiology and its quality attributes - K. K. Srivastava; Sumit K. Soni; Dinesh Kumar; S. K. Dwivedi (Plant Physiology Reports, 2023)

Recent advances in 3D slope stability analysis: a detailed review - Sumit Kumar; Shiva Shankar Choudhary; Avijit Burman (Modeling Earth Systems and Environment, 2023)

Itraconazole Confers Cytoprotection Against Neurodegenerative Disease-Associated Abnormal Protein Aggregation - Ankur Rakesh Dubey; Ribhav Mishra; Yuvraj Anandrao Jagtap; Sumit Kinger; Prashant Kumar; Rohan Dhiman; Somnath Ghosh; Sarika Singh; Amit Prasad; Nihar Ranjan Jana; Amit Mishra (Molecular Neurobiology, 2023)

Elucidation of Heat Shock Transcription Factor Family (HSFs) Postulates Significant Insights for the Identification of Their Putative Roles in Root Development and Hormonal Regulation in Tomato - Adity Majee; Vinod Kumar; Nasreen Bano; Anjana Kumari; Sumit Kumar Bag; Vidhu A. Sane (Journal of Plant Growth Regulation, 2023)

Hexavalent chromium-reducing plant growth-promoting rhizobacteria are utilized to bio-fortify trivalent chromium in fenugreek by promoting plant development and decreasing the toxicity of hexavalent chromium in the soil - Sumit K. Soni; Govind Kumar; Anju Bajpai; Rakshapal Singh; Yashi Bajapi; Laxmi; Sudeep Tiwari (Journal of Trace Elements in Medicine and Biology, 2023)

Trichoderma viride—Mediated Modulation of Oxidative Stress Network in Potato Challenged with Alternaria solani - Sumit Kumar; Ram Chandra; Chetan Keswani; Tatiana Minkina; Saglara Mandzhieva; Marina Voloshina; Mukesh Meena (Journal of Plant Growth Regulation, 2023)

4D nanoprinted sensor for facile organo-arsenic detection: A two-photon lithography-based approach - Sweta Rani; Rahul Kumar Das; Arun Jaiswal; Gaurav Pratap Singh; Ajinkya Palwe; Sumit Saxena; Shobha Shukla (Chemical Engineering Journal, 2023)

Therapeutic modulation of JAK-STAT, mTOR, and PPAR-γ signaling in neurological dysfunctions - Sumit Kumar; Sidharth Mehan; Acharan S. Narula (Journal of Molecular Medicine, 2023)

Timmiella goaense gen. n., sp. n. (Nematoda: Dorylaimida: Belondiroidea) from Western Ghats of India - Sumit Kumar; Wasim Ahmad (Biologia, 2023)

Role of morphology and chemical composition of PM for particle deposition in human respiratory system: A case study over megacity-Delhi - Sadaf Fatima; Sumit Kumar Mishra; Uma Kumar; Ajit Ahlawat; Tulsi Satyavir Dabodiya; Dheeraj Khosla (Urban Climate, 2023)

Synergy of green hydrogen sector with offshore industries: Opportunities and challenges for a safe and sustainable hydrogen economy - Sumit Kumar; Til Baalisampang; Ehsan Arzaghi; Vikram Garaniya; Rouzbeh Abbassi; Fatemeh Salehi (Journal of Cleaner Production, 2023)

Mass transfer kinetics and quality evaluation of tomato seed oil extracted using emerging technologies - Sumit Kumar; S. Nirmal Thirunavookarasu; C.K. Sunil; S. Vignesh; N. Venkatachalapathy; Ashish Rawson (Innovative Food Science & Emerging Technologies, 2023)

Landfill leachate valorization: A potential alternative to burden off resources and support energy systems - Smita S. Kumar; Amit Kumar; Sandeep K. Malyan; Pooja Ghosh; Madan Kumar; Rimika Kapoor; Ajay Kumar Agrawal; Sumit Kumar; Vivek Kumar; Lakhveer Singh (Fuel, 2023)

Application of Innovative Machine Learning Techniques for Long-Term Rainfall Prediction - Suman Markuna; Pankaj Kumar; Rawshan Ali; Dinesh Kumar Vishwkarma; Kuldeep Singh Kushwaha; Rohitashw Kumar; Vijay Kumar Singh; Sumit Chaudhary; Alban Kuriqi (Pure and Applied Geophysics, 2023)

Antimicrobial and Cytotoxic Potential of Helminthosporin from Rumex abyssiniscus Jacq. Discovered as a Novel Source of Syringic Acid and Bis(2-ethyloctyl) Phthalate - Augustin Ntemafack; Arem Qayum; Shakti Kumar Dhiman; Michel-Gael Fofack Guefack; Sonia Thapa; Brice Elvis Nougan Wamba; Victor Kuete; Shashank K. Singh; Sandip B. Bharate; Qazi Parvaiz Hassan; Sumit G. Gandhi (Current Microbiology, 2023)

Heat storage material: a hope in solar thermal - Ravin Sehrawat; Ravinder Kumar Sahdev; Sumit Tiwari (Environmental Science and Pollution Research, 2022)

Cow-urine emulsified diesel fuel: preparation, stability, and rheological study for diesel engine application - Amit Jhalani; Sumit Sharma; Digambar Singh; Pushpendra Kumar Sharma (Environmental Science and Pollution Research, 2022)

In vivo therapeutic efficacy of Curcuma longa extract loaded ethosomes on wound healing - Sumit Kumar; Akhilesh Kumar; Naveen Kumar; Praveen Singh; Thakur Uttam Singh; Bhoj Raj Singh; Piyush Kumar Gupta; Vijay Kumar Thakur (Veterinary Research Communications, 2022)

Tubby-like proteins (TLPs) transcription factor in different regulatory mechanism in plants: a review - Nasreen Bano; Shahre Aalam; Sumit Kumar Bag (Plant Molecular Biology, 2022)

Synthesis and in vitro SAR evaluation of natural vanillin-based chalcones tethered quinolines as antiplasmodial agents - Nitin H. Andhare; Mohammad Anas; Sumit K. Rastogi; Ashan Manhas; Yogesh Thopate; Kumkum Srivastava; Niti Kumar; Arun K. Sinha (Medicinal Chemistry Research, 2022)

Avian Haemosporidian (Plasmodium and Haemoproteus) Status in Two Bird Groups (Old-World Flycatchers and Thrushes) of India and Their Phylogenetic Relationships with Other Lineages of the World - Vipin; Ashutosh Singh; Vinita Sharma; Narinder Kumar Tripathi; Rajnikant Dixit; Bhim Singh; Chandra Prakash Sharma; Sumit G. Gandhi; Dhananjai Mohan; Sandeep Kumar Gupta (Acta Parasitologica, 2022)

An eco-friendly corrosion inhibitor Cuscuta reflexa extract and PEG400 for mild steel inhibition in acidic medium: computational and experimental investigations - Priti Pahuja; Meena Yadav; Monika Dhanda; Rajat Arora; Simran Ahlawat; Ajay Satija; Neeru Jhanjhariya; Sumit Kumar; Suman Lata (Environmental Science and Pollution Research, 2022)

A comprehensive and quantitative assessment of Raunthi Gad flash flood, Rishi Ganga catchment, central Himalaya, Uttarakhand, India - Harish Chandra Nainwal; R. Shankar; Aditya Mishra; Sumit Mishra; Ankit Pandey; Sunil Singh Shah; Gambhir Singh Chauhan; Deepak Kumar (Natural Hazards, 2022)

Data mining of transcriptional biomarkers at different cotton fiber developmental stages - Priti Prasad; Uzma Khatoon; Rishi Kumar Verma; Samir V Sawant; Sumit K Bag (Functional & Integrative Genomics, 2022)

Genome-wide association mapping for identification of sheath blight resistance loci from wild rice Oryza rufipogon - Sumit K. Aggarwal; Palvi Malik; Kumari Neelam; Kishor Kumar; Rupinder Kaur; Jagjeet S. Lore; Kuldeep Singh (Euphytica, 2022)

Profiling microbiota in Guts of Three Brachyuran Crab Species of Indian Sundarbans - Missidona Biswas; Anupam Podder; Soumyadip Panja; Atreyee Chaudhuri; Asish Kumar Mukhopadhyay; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2022)

Transmission dynamics of Monkeypox virus: a mathematical modelling approach - Olumuyiwa James Peter; Sumit Kumar; Nitu Kumari; Festus Abiodun Oguntolu; Kayode Oshinubi; Rabiu Musa (Modeling Earth Systems and Environment, 2022)

Microbial Journey: Mount Everest to Mars - Utkarsh Sood; Gauri Garg Dhingra; Shailly Anand; Princy Hira; Roshan Kumar; Jasvinder Kaur; Mansi Verma; Nirjara Singhvi; Sukanya Lal; Charu Dogra Rawat; Vineet Kumar Singh; Jaspreet Kaur; et al. (Indian Journal of Microbiology, 2022)

Molecular pathogenesis of Japanese encephalitis and possible therapeutic strategies - Sanjay Kumar; Akanksha Verma; Pardeep Yadav; Sumit Kumar Dubey; Esam Ibraheem Azhar; S. S. Maitra; Vivek Dhar Dwivedi (Archives of Virology, 2022)

Protective effect of Bacillus species associated with Rumex dentatus against postharvest soil borne disease in potato tubers and GC–MS metabolite profile - Augustin Ntemafack; Rekha Chouhan; Nitika Kapoor; Amit Kumar; Shakti Kumar Dhiman; Ravi Singh Manhas; Asha Chaubey; Qazi Parvaiz Hassan; Sumit G. Gandhi (Archives of Microbiology, 2022)

Melatonin induces apoptosis and cell cycle arrest in cervical cancer cells via inhibition of NF-κB pathway - Tarun Minocha; Megha Das; Vipin Rai; Sumit Singh Verma; Nikee Awasthee; Subash Chandra Gupta; Chandana Haldar; Sanjeev Kumar Yadav (Inflammopharmacology, 2022)

An integration of health risk indices and statistical techniques to appraise the associated human risks and source apportionment of potentially toxic elements in roadside soils - Vinod Kumar; Shevita Pandita; Sumit Singh; Anket Sharma (Arabian Journal of Geosciences, 2022)

Characterization of Power Ultrasound Modified Kappaphycus alvarezii Biosorbent and its Modeling by Artificial Neural Networks - Sumit Kumar; S. Nisanth Manokar; Nirmal Thirunavookarasu; V. Nivethitha; T. N. Nidhusri; T. Niranjana; C. K. Sunil; S. Vignesh; Arunkumar Anandharaj; Ashish Rawson (Water, Air, & Soil Pollution, 2022)

Luminescent Features of Ternary Europium Complexes: Photophysical and Optoelectronic Evaluation - Anjli Hooda; Kapeesha Nehra; Anuj Dalal; Shri Bhagwan; Isha Gupta; Devender Singh; Sumit Kumar (Journal of Fluorescence, 2022)

Red-emitting β-diketonate Eu(III) Complexes With Substituted 1,10-phenanthroline Derivatives: Optoelectronic and Spectroscopic Analysis - Anjli Hooda; Anuj Dalal; Kapeesha Nehra; Sitender Singh; Sumit Kumar; Devender Singh (Journal of Fluorescence, 2022)

Role of JAK-STAT and PPAR-Gamma Signalling Modulators in the Prevention of Autism and Neurological Dysfunctions - Rishabh Khera; Sidharth Mehan; Sumit Kumar; Pranshul Sethi; Sonalika Bhalla; Aradhana Prajapati (Molecular Neurobiology, 2022)

Improper Proteostasis: Can It Serve as Biomarkers for Neurodegenerative Diseases? - Ankur Rakesh Dubey; Som Mohanlal Patwa; Sumit Kinger; Yuvraj Anandrao Jagtap; Prashant Kumar; Sarika Singh; Rohan Dhiman; Hem Chandra Jha; Amit Mishra (Molecular Neurobiology, 2022)

Development of near isogenic lines for grain softness through marker assisted backcross breeding in wheat - Tej Pratap Jitendra Kumar; Anjali Rai; Sumit K. Singh; Rajeev Ranjan Kumar; Arvind K. Ahlawat; Savita Saini; R. B. Shukla; Namita Bedi; Anju Mahendru-Singh (Journal of Plant Biochemistry and Biotechnology, 2022)

Improved skill of NCMRWF Unified Model (NCUM-G) in forecasting tropical cyclones over NIO during 2015–2019 - Sushant Kumar; Anumeha Dube; Sumit Kumar; S Indira Rani; Kuldeep Sharma; S Karunasagar; Saji Mohandas; Raghavendra Ashrit; John P George; Ashis K Mitra (Journal of Earth System Science, 2022)

Property-enhanced paraffin-based composite phase change material for thermal energy storage: a review - Durgesh Kumar Mishra; Chiranjib Bhowmik; Sumit Bhowmik; Krishna Murari Pandey (Environmental Science and Pollution Research, 2022)

Study of variation of aerosol optical properties over a high altitude station in Indian Western Himalayan region, palampur using raman lidar system - Shishir Kumar Singh; S. R. Radhakrishnan; Jaswant; Sumit Kumar Mishra; Devesh Kumar Shukla; Ashish Ranjan; Chhemendra Sharma (Journal of Atmospheric Chemistry, 2022)

Microbial production of multienzyme preparation from mosambi peel using Trichoderma asperellum - Balvindra Singh; Neelima Garg; Priti Mathur; Sumit K. Soni; Supriya Vaish; Sanjay Kumar (Archives of Microbiology, 2022)

A Charge Variant of Bevacizumab Offers Enhanced FcRn-Dependent Pharmacokinetic Half-Life and Efficacy - Sumit K. Singh; Deepak Kumar; Saurabh Nagpal; Sunil K. Dubey; Anurag S. Rathore (Pharmaceutical Research, 2022)

Synthesis, Optoelectronic and Photoluminescent Characterizations of Green Luminous Heteroleptic Ternary Terbium Complexes - Anuj Dalal; Kapeesha Nehra; Anjli Hooda; Sitender Singh; Devender Singh; Sumit Kumar (Journal of Fluorescence, 2022)

A comprehensive review on biodiversity information portals - Sameer Saran; Sumit Kumar Chaudhary; Priyanka Singh; Amrapali Tiwari; Vishal Kumar (Biodiversity and Conservation, 2022)

Metagenomic insights into the environmental adaptation and metabolism of Candidatus Haloplasmatales, one archaeal order thriving in saline lakes - Heng Zhou; Dahe Zhao; Shengjie Zhang; Qiong Xue; Manqi Zhang; Haiying Yu; Jian Zhou; Ming Li; Sumit Kumar; Hua Xiang (Environmental Microbiology, 2022)
Summary The KTK 4A‐related Thermoplasmata thrives in the sediment of saline lakes; however, systematic research on its taxonomy, environmental adaptation and metabolism is lacking. Here, we detected this abundant lineage in the sediment of five artificially separated ponds (salinity 7.0%–33.0%) within a Chinese soda‐saline lake using culture‐independent metagenomics and archaeal 16S rRNA gene amplicons. The phylogenies based on the 16S rRNA gene, and 122 archaeal ubiquitous single‐copy proteins and genome‐level identity analyses among the metagenome‐assembled genomes demonstrate this lineage forming a novel order, Candidatus Haloplasmatales, comprising four genera affiliated with the identical family. Isoelectric point profiles of predicted proteomes suggest that most members adopt the energetically favourable ‘salt‐in’ strategy. Functional prediction indicates the lithoheterotrophic nature with the versatile metabolic potentials for carbohydrate and organic acids as well as carbon monoxide and hydrogen utilization. Additionally, hydrogenase genes hdrABC ‐ mvhADG are linked with incomplete reductive citrate cycle genes in the genomes, suggesting their functional connection. Comparison with the coupling of HdrABC‐MvhADG and methanogenesis pathway provides new insights into the compatibility of laterally acquired methanogenesis with energy metabolism in the related order Methanomassiliicoccales . Globally, our research sheds light on the taxonomy, environmental adaptative mechanisms, metabolic potentials and evolutional significance of Ca . Haloplasmatales.

Genome-wide profiling of drought-tolerant Arabidopsis plants over-expressing chickpea MT1 gene reveals transcription factors implicated in stress modulation - Sanoj Kumar; Ankita Yadav; Nasreen Bano; Arvind Kumar Dubey; Rita Verma; Ankesh Pandey; Anil Kumar; Sumit Bag; Sudhakar Srivastava; Indraneel Sanyal (Functional & Integrative Genomics, 2022)

Performance assessment of conventional solar desalination system in Northern part of Gujarat - Pranav Mehta; Abd Elnaby Kabeel; Vivek Patel; Sumit Kumar (Environmental Science and Pollution Research, 2022)

Hydrochemical characteristics and water quality indices‐based assessment of River Kali for agricultural irrigation in northern India * - Gaurav Singh; Neelam Patel; Tanu Jindal; Manju Rawat Ranjan; Sumit Pal; Jitendra Ahirwal; Swatantra Kumar Dubey (Irrigation and Drainage, 2022)
High‐quality water is required to produce a greater crop yield. River water is a major source of irrigation; however, in several densely populated countries, it is severely polluted due to anthropogenic activities. We aim to assess the Kali River water quality from 17 sampling stations using hydrochemical characterization in western Uttar Pradesh during the pre‐ and post‐monsoon seasons. The suitability of river water quality for agricultural irrigation was determined by water quality indices such as sodium adsorption ratio (SAR), sodium percentage (Na%), residual sodium carbonate (RSC), permeability index (PI), magnesium ratio (MR), and Kelley's index (KI). Results of the study showed that water quality in terms of pH, electrical conductivity, total dissolved solids, Cl − , SAR, and MR is moderately suitable for agricultural irrigation. However, only 64.7% (NO 3 − N), 88.2% (HCO 3 − ), and 70.6% (B) samples in pre‐monsoon and 70.6% (NO 3 − N), 100% (HCO 3 − ), and 64.7% (B) samples in post‐monsoon were acceptable for irrigation. In addition, 94.1%, 23.5%, and 70.6% of samples in pre‐monsoon and 82.4%, 17.6%, and 23.5% of samples in post‐monsoon analysed for Na%, RSC, PI, and KI, respectively, were found suitable for irrigation. The analysis of selected water quality parameters and water quality indices shows that Kali River water is polluted at the downstream side, and its suitability for agricultural irrigation varies with the season.

Dual Trichoderma consortium mediated elevation of systemic defense response against early blight in potato - Sumit Kumar; Ram Chandra; Lopamudra Behera; Chetan Keswani; Estibaliz Sansinenea (European Journal of Plant Pathology, 2022)

Rapid determination and optimisation of berberine from Himalayan Berberis lycium by soxhlet apparatus using CCD-RSM and its quality control as a potential candidate for COVID-19 - Anil Kumar Katare; Bikarma Singh; Pooja Shukla; Sandeep Gupta; Bishander Singh; Kavya Yalamanchili; Nitin Kulshrestha; Rajendra Bhanwaria; Ashok Kumar Sharma; Sarita Sharma; Sneha; Durga Prasad Mindala; et al. (Natural Product Research, 2022)

Rhabdonatronobacter sediminivivens gen. nov., sp. nov. isolated from the sediment of Hutong Qagan Soda Lake - Heng Zhou; Ming Yang; Qiong Xue; Sumit Kumar; Shengjie Zhang; Jian Zhou; Dahe Zhao; Hua Xiang (Archives of Microbiology, 2022)

Soil Properties, Litter Dynamics and Biomass Carbon Storage in Three-Bamboo Species of Sub-Himalayan Region of Eastern India - P. Surath Kumar; Gopal Shukla; Arun Jyoti Nath; Sumit Chakravarty (Water, Air, & Soil Pollution, 2022)

Assessment of Functional Characterization and Comparability of Biotherapeutics: a Review - Rozaleen Dash; Sumit Kumar Singh; Narendra Chirmule; Anurag S. Rathore (The AAPS Journal, 2022)

Identification of miRNA and their target genes in Cestrum nocturnum L. and Cestrum diurnum L. in stress responses - Nasreen Bano; Shafquat Fakhrah; Sagar Prasad Nayak; Sumit Kumar Bag; Chandra Sekhar Mohanty (Physiology and Molecular Biology of Plants, 2022)

Assessment of water quality condition and spatiotemporal patterns in selected wetlands of Punjab, India - Yadvinder Singh; Gurdarshan Singh; Jasvirinder Singh Khattar; Sophia Barinova; Jasneet Kaur; Sumit Kumar; Davinder Pal Singh (Environmental Science and Pollution Research, 2022)

Mesenchymal stem cells are prospective novel off-the-shelf wound management tools - Poonam Malhotra; Manish Shukla; Poonam Meena; Anupama Kakkar; Nitin Khatri; Rakesh K Nagar; Mukesh Kumar; Sumit K Saraswat; Supriya Shrivastava; Rajan Datt; Siddharth Pandey (Drug Delivery and Translational Research, 2022)

Risk estimation of soil slope stability problems - Guru Das; Avijit Burman; Abidhan Bardhan; Sumit Kumar; Shiva Shankar Choudhary; Pijush Samui (Arabian Journal of Geosciences, 2022)

An analytic model of Rayleigh waves transference in a fluid containing inhomogeneity as a circular function of depth - Tapas Ranjan Panigrahi; Sumit Kumar Vishwakarma; Rupinderjit Kaur (Journal of Earth System Science, 2021)

Establishment of virus-free elite mother orchards of apple in the Trans-Himalayan region of India - Santosh Watpade; Rakesh Kumar; Pooja Bhardwaj; Kallol Kumar Pramanick; Arun Kumar Shukla; Baswaraj Raigond; Jitender Kumar; Usha Sharma; Sumit Vashisth; Sudhir Verma (Indian Phytopathology, 2021)

Isolation optimisation, synthesis, molecular docking and in silico ADMET studies of lantadene a and its derivatives - Sharad Kumar Suthar; Ajay Hooda; Ankesh Sharma; Sumit Bansal; Jitender Monga; Monika Chauhan; Manu Sharma (Natural Product Research, 2021)

Synthesis and Characterization of Chitosan-Alginate-Based Cross-linked Copolymer for the Effective Removal of Methylene Blue from Its Aqueous Solution - Sumit Kumar; Shailesh Kumar; Ashok Kumar; Swati Rastogi; Deepak Kumar (Water, Air, & Soil Pollution, 2021)

Role of Space-Borne Sea Surface Winds on the Simulation of Tropical Cyclones Over the Indian Seas - M. T. Bushair; S. Indira Rani; Gibies George; Sushant Kumar; Sumit Kumar; John. P. George (Pure and Applied Geophysics, 2021)

Dynamics of Zea mays transcriptome in response to a polyphagous herbivore, Spodoptera litura - Archana Singh; Sujata Singh; Ragini Singh; Sumit Kumar; Sanjay Kumar Singh; Indrakant Kumar Singh (Functional & Integrative Genomics, 2021)

Modeling the mechanical vibrations of Rayleigh surface wave in a medium exhibiting heterogeneity as elementary transcendental functions of depth - Rupinderjit Kaur; Sumit Kumar Vishwakarma (Arabian Journal of Geosciences, 2021)

Evaluation of the benefits of assimilation of Meteosat-8 observations in an NWP system over the Indian Ocean region - M. T. Bushair; S. Indira Rani; Buddhi Prakash Jangid; Priti Sharma; Sumit Kumar; John. P. George; M. Das Gupta (Meteorology and Atmospheric Physics, 2021)

Isolation and biochemical characterization of a novel serine protease identified from solid tannery waste metagenome - Sumit Kumar Verma; Prakash Chand Sharma (Biologia, 2021)

Cyclic siloxane biosurfactant-producing Bacillus cereus BS14 biocontrols charcoal rot pathogen Macrophomina phaseolina and induces growth promotion in Vigna mungo L. - Sumit Kumar; Shrivardhan Dheeman; Ramesh C. Dubey; Dinesh K. Maheshwari; Nitin Baliyan (Archives of Microbiology, 2021)

Distribution and Abundance of Raptors in Kailash Sacred Landscape, Western Himalaya, India - Sumit Kumar Arya; Gopal Singh Rawat; Govindan Veeraswami Gopi (Proceedings of the Zoological Society, 2021)

Genome-wide identification, phylogeny, and expression analysis of the bHLH gene family in tobacco (Nicotiana tabacum) - Nasreen Bano; Preeti Patel; Debasis Chakrabarty; Sumit Kumar Bag (Physiology and Molecular Biology of Plants, 2021)

Role of vitamins and minerals as immunity boosters in COVID-19 - Puneet Kumar; Mandeep Kumar; Onkar Bedi; Manisha Gupta; Sachin Kumar; Gagandeep Jaiswal; Vikrant Rahi; Narhari Gangaram Yedke; Anjali Bijalwan; Shubham Sharma; Sumit Jamwal (Inflammopharmacology, 2021)

Geo-morphometric prioritization of Aglar micro watershed in Lesser Himalaya using GIS approach - Vikram Kumar; Sumit Sen; Pankaj Chauhan (Modeling Earth Systems and Environment, 2021)

A hydroponic-based efficient hardening protocol for in vitro raised commercial kiwifruit (Actinidia deliciosa) - Sumit Purohit; Janhvi Mihra Rawat; Vivek Kumar Pathak; Dinesh Kumar Singh; Balwant Rawat (In Vitro Cellular & Developmental Biology - Plant, 2021)

Dust induced radiative perturbations during an episode of long-range dust transport over Delhi, India: a high-resolution regional NWP model study - Timmy Francis; A. Jayakumar; Jisesh Sethunadh; Saji Mohandas; Sumit Kumar; E. N. Rajagopal (Meteorology and Atmospheric Physics, 2021)

Study of cyclogenesis of developing and non-developing tropical systems of NIO using NCUM forecasting system - V. P. M. Rajasree; A. Routray; John P. George; Sumit Kumar; Amit P. Kesarkar (Meteorology and Atmospheric Physics, 2021)

Diversity, community characteristics and regeneration status of tree species in Rowa Wildlife Sanctuary: an Indo-Burmese Hotspot—Tripura, North East India - Bimal Debnath; Sumit Kumar Das; Amal Debnath (Vegetos, 2021)

A Comprehensive Review on 1st-Generation Biodiesel Feedstock Palm Oil: Production, Engine Performance, and Exhaust Emissions - Digambar Singh; Dilip Sharma; S. L. Soni; Chandrapal Singh Inda; Sumit Sharma; Pushpendra Kumar Sharma; Amit Jhalani (BioEnergy Research, 2021)

Dynamics of SV-wave, SH-wave, and P-wave in a cross-anisotropic medium exhibiting exponential heterogeneity - Sumit Kumar Vishwakarma; Tapas Ranjan Panigrahi (Arabian Journal of Geosciences, 2021)

Advances and clinical challenges for translating nerve conduit technology from bench to bed side for peripheral nerve repair - Poonam Meena; Anupama Kakkar; Mukesh Kumar; Nitin Khatri; Rakesh Kumar Nagar; Aarti Singh; Poonam Malhotra; Manish Shukla; Sumit Kumar Saraswat; Supriya Srivastava; Rajan Datt; Siddharth Pandey (Cell and Tissue Research, 2021)

Chemo-informatics guided study of natural inhibitors targeting rho GTPase: a lead for treatment of glaucoma - Sumit Kumar Rai; Rajesh Kumar Pathak; Dev Bukhsh Singh; Arun Bhatt; Mamta Baunthiyal (In Silico Pharmacology, 2021)

Exploring the molecular approach of COX and LOX in Alzheimer’s and Parkinson’s disorder - Arun Kumar; Tapan Behl; Sumit Jamwal; Ishnoor Kaur; Archit Sood; Puneet Kumar (Molecular Biology Reports, 2020)

Land subsidence mapping and monitoring using modified persistent scatterer interferometric synthetic aperture radar in Jharia Coalfield, India - Sunil Kumar; Dheeraj Kumar; Sumit Kumar Chaudhary; Narendra Singh; Kapil Kumar Malik (Journal of Earth System Science, 2020)

Overexpression of wheat transcription factor (TaHsfA6b) provides thermotolerance in barley - Anuj Kumar Poonia; Sumit Kumar Mishra; Parul Sirohi; Reeku Chaudhary; Meenakshi Kanwar; Hugo Germain; Harsh Chauhan (Planta, 2020)

Understanding Oxidation Propensity in GCSF and Assessment of its Safety and Efficacy - Sumit Kumar Singh; Deepak Kumar; Anurag S. Rathore (Pharmaceutical Research, 2020)

Cartilage repair using stem cells & biomaterials: advancement from bench to bedside - Anupama Kakkar; Aarti Singh; Sumit Kumar Saraswat; Supriya Srivastava; Nitin Khatri; Rakesh Kumar Nagar; Mukesh Kumar; Poonam Meena; Rajan Datt; Siddharth Pandey (Molecular Biology Reports, 2020)

Epoxyazadiradione exhibit activities in head and neck squamous cell carcinoma by targeting multiple pathways - Vipin Rai; Sushil Kumar Aggarwal; Sumit Singh Verma; Nikee Awasthee; Anupam Dhasmana; Sadhna Aggarwal; Satya N. Das; Mangalam S. Nair; Sanjay Yadav; Subash C. Gupta (Apoptosis, 2020)

Soil erosion and flood hazard zonation using morphometric and morphotectonic parameters in Upper Alaknanda river basin - Neeraj Pant; Rajendra Kumar Dubey; Anand Bhatt; Shive Prakash Rai; Prabhat Semwal; Sumit Mishra (Natural Hazards, 2020)

Protective Effect of Hemin Against Experimental Chronic Fatigue Syndrome in Mice: Possible Role of Neurotransmitters - Vandana Thakur; Sumit Jamwal; Mandeep Kumar; Vikrant Rahi; Puneet Kumar (Neurotoxicity Research, 2020)

Insights into the metabolism pathway and functional genes of long-chain aliphatic alkane degradation in haloarchaea - Sumit Kumar; Jian Zhou; Ming Li; Hua Xiang; Dahe Zhao (Extremophiles, 2020)

Self-cleansing properties of Ganga during mass ritualistic bathing on Maha-Kumbh - Sanjay Dwivedi; Puneet Singh Chauhan; Seema Mishra; Amit Kumar; Pradyumna Kumar Singh; Mohan Kamthan; Reshu Chauhan; Surabhi Awasthi; Sumit Yadav; Aradhana Mishra; Shekhar Mallick; Sanjeev Kumar Ojha; et al. (Environmental Monitoring and Assessment, 2020)

The Potato Tuber Moth, Phthorimaea operculella (Zeller), in India: Biology, Ecology, and Control - R. S. Chandel; Sumit Vashisth; Saurbh Soni; Rahul Kumar; Vinod Kumar (Potato Research, 2020)

Comparison Between Immuno-Clinicopathological Features of Experimental and Human Visceral Leishmaniasis by Leishmania donovani - Sheetal Saini; Anuradha Dube; Amogh Anant Sahasrabuddhe; Chandreshwar Prasad Thakur; Sumit Joshi; Keerti Rawat; Ambak Kumar Rai (Acta Parasitologica, 2020)

Detection and Analysis of Coal Fire in Jharia Coalfield (JCF) Using Landsat Remote Sensing Data - Rakesh Kumar Mishra; Jai Krishna Pandey; Jitendra Pandey; Sumit Kumar; Paresh Nath Singha Roy (Journal of the Indian Society of Remote Sensing, 2020)

Occurrence and variability of begomoviruses associated with bhendi yellow vein mosaic and okra enation leaf curl diseases in south-western India - Madhvi Naresh; Zainul Abdeen Khan; Rohit Kumar; Sumit P. Kale; Vijay M. Patil; Jaising C. Rajput; Indranil Dasgupta (VirusDisease, 2019)

Controlling pathogenesis in Candida albicans by targeting Efg1 and Glyoxylate pathway through naturally occurring polyphenols - Sonali Mishra; Sumit Kumar Rastogi; Sangeeta Singh; Sneh Lata Panwar; Manoj Kumar Shrivash; Krishna Misra (Molecular Biology Reports, 2019)

Medical image encryption using fractional discrete cosine transform with chaotic function - Sumit Kumar; Bhaskar Panna; Rajib Kumar Jha (Medical & Biological Engineering & Computing, 2019)

Oral administration of graphene oxide nano-sheets induces oxidative stress, genotoxicity, and behavioral teratogenicity in Drosophila melanogaster - Subhashree Priyadarsini; Shraban Kumar Sahoo; Swetapadma Sahu; Sumit Mukherjee; Garudadhwaj Hota; Monalisa Mishra (Environmental Science and Pollution Research, 2019)

In Vitro Analysis of Bacosine as Novel Therapeutic Agent for Murine Breast Cancer - Sumit Ranjan Mishra; Pavan Kumar Yadav; Perumal Nandhakumar; Mohini Saini; Ajay Kumar; Meena Kataria (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Petrographic controls on phosphorous distribution in coal seams of the Jharia basin, India - Atul Kumar Varma; Sumit Mishra; Balram Tiwari; Bodhisatwa Hazra; Susheel Kumar; Durga Charan Panigrahi; Anwita Ojha (Journal of Earth System Science, 2019)

Correction to: First report of edible mushroom Pleurotus ostreatus from India with potential to kill plant parasitic nematodes - R. K. Singh; Sumit Kumar Pandey; Dalel Singh; Prahlad Masurkar (Indian Phytopathology, 2019)

Interplay of phosphorus doses, cyanobacterial inoculation, and elevated carbon dioxide on yield and phosphorus dynamics in cowpea - Sumit Kumar Dey; B. Chakrabarti; T. J. Purakayastha; Radha Prasanna; R. Mittal; S. D. Singh; H. Pathak (Environmental Monitoring and Assessment, 2019)

Radiation hazards associated with radionuclides and theoretical evaluation of indoor radon concentration from soil exhalation of Udhampur District, Jammu and Kashmir State, India - Sumit Sharma; Ajay Kumar; Rohit Mehra; Rosaline Mishra (Journal of Soils and Sediments, 2019)

First report of edible mushroom Pleurotus ostreatus from India with potential to kill plant parasitic nematodes - R. K. Singh; Sumit Kumar Pandey; Dalel Singh; Prahlad Masurkar (Indian Phytopathology, 2019)

A comprehensive review on water-emulsified diesel fuel: chemistry, engine performance and exhaust emissions - Amit Jhalani; Dilip Sharma; Shyam Lal Soni; Pushpendra Kumar Sharma; Sumit Sharma (Environmental Science and Pollution Research, 2019)

SH-wave propagation in linearly varying fiber-reinforced viscoelastic composite structure uninitial stress - Sumit Kumar Vishwakarma; Tapas Ranjan Panigrahi; Rupinderjit Kaur (Arabian Journal of Geosciences, 2019)

Current Status of Stem Cell Treatment for Type I Diabetes Mellitus - Anupama Kakkar; Ashima Sorout; Mahak Tiwari; Pallavi Shrivastava; Poonam Meena; Sumit Kumar Saraswat; Supriya Srivastava; Rajan Datt; Siddharth Pandey (Tissue Engineering and Regenerative Medicine, 2018)

Assessment of Soil Gas Radon and Exhalation Studies in Lower Himalayan Region of Jammu and Kashmir State, India - Sumit Sharma; Ajay Kumar; Rohit Mehra; Rosaline Mishra (Pure and Applied Geophysics, 2018)

Probiotic Effect of Bacillus licheniformis fb11 on the Digestive Efficiency and Growth Performance in Juvenile Chitala chitala (Hamilton, 1822) - Anisa Mitra; Pratap Kumar Mukhopadhyay; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2018)

DNA binding, cleavage and cytotoxicity studies of three mononuclear Cu(II) chloro-complexes containing N–S donor Schiff base ligands - Sidhali U. Parsekar; Joseph Fernandes; Arnab Banerjee; Om Prakash Chouhan; Sumit Biswas; Manohar Singh; Durga P. Mishra; Manjuri Kumar (JBIC Journal of Biological Inorganic Chemistry, 2018)

Assessment of radionuclide concentration and exhalation studies in soil of lesser Himalayas of Jammu and Kashmir, India - Ajay Kumar; Raman Vij; Sumit Sharma; Amit Sarin; Saurabh Narang (Acta Geophysica, 2018)

Evaluation of spring discharge dynamics using recession curve analysis: a case study in data-scarce region, Lesser Himalayas, India - Vikram Kumar; Sumit Sen (Sustainable Water Resources Management, 2018)

An Overview of Biology And Culture Potentials of Humped Featherback Chitala chitala (Hamilton, 1822) – A New Candidate for Aquaculture Diversification - Anisa Mitra; Pratap Kumar Mukhopadhyay; Sumit Homechaudhuri (Reviews in Fisheries Science & Aquaculture, 2018)

Assessment of progeny concentrations of 222Rn/220Rn and their related doses using deposition-based direct progeny sensors - Sumit Sharma; Ajay Kumar; Rohit Mehra; Manpreet Kaur; Rosaline Mishra (Environmental Science and Pollution Research, 2018)

Assessment of radon concentration and heavy metal contamination in groundwater of Udhampur district, Jammu & Kashmir, India - Ajay Kumar; Sumit Sharma; Rohit Mehra; Priya Kanwar; Rosaline Mishra; Inderpreet Kaur (Environmental Geochemistry and Health, 2018)

Profile of Digestive Enzymes Activity During Early Development of Featherback Chitala chitala (Hamilton, 1822) - Anisa Mitra; Pratap Kumar Mukhopadhyay; Sumit Homechaudhuri (Proceedings of the Zoological Society, 2017)

Riboflavin and health: A review of recent human research - Kiran Thakur; Sudhir Kumar Tomar; Ashish Kumar Singh; Surajit Mandal; Sumit Arora (Critical Reviews in Food Science and Nutrition, 2017)

Determination of Critical Quality Attributes for a Biotherapeutic in the QbD Paradigm: GCSF as a Case Study - Sumit K. Singh; Deepak Kumar; Anurag S. Rathore (The AAPS Journal, 2017)

Isolation and complete genome sequence of Halorientalis hydrocarbonoclasticus sp. nov., a hydrocarbon-degrading haloarchaeon - Dahe Zhao; Sumit Kumar; Jian Zhou; Rui Wang; Ming Li; Hua Xiang (Extremophiles, 2017)

Assessment of air quality in Haora River basin using fuzzy multiple-attribute decision making techniques - Ajit Pratap Singh; Sumanta Chakrabarti; Sumit Kumar; Anjaney Singh (Environmental Monitoring and Assessment, 2017)

Characterization of a bacterioferritin comigratory protein family 1-Cys peroxiredoxin from Candidatus Liberibacter asiaticus - Anamika Singh; Narender Kumar; Prabhat P. S. Tomar; Sumit Bhose; Dilip Kumar Ghosh; Partha Roy; Ashwani K. Sharma (Protoplasma, 2017)

Evaluation of carbofuran-mediated toxicity against human lymphocytes and red blood cells in simulated wastewater degraded by coagulation–flocculation - Roli Saini; Pradeep Kumar; Sumit Kumar Hira; Partha Pratim Manna (Environmental Science and Pollution Research, 2017)

L-theanine, a Component of Green Tea Prevents 3-Nitropropionic Acid (3-NP)-Induced Striatal Toxicity by Modulating Nitric Oxide Pathway - Sumit Jamwal; Puneet Kumar (Molecular Neurobiology, 2017)

Verification of dust forecast over the Indian region with satellite and ground based observations - Prasenjit Das; John P. George; Sumit Kumar (International Journal of Remote Sensing, 2016)

Magnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)

Farmers perception and awareness of climate change: a case study from Kanchandzonga Biosphere Reserve, India - Gopal Shukla; Ashok Kumar; Nazir A. Pala; Sumit Chakravarty (Environment, Development and Sustainability, 2016)

Maximizing Shelf Life of Paneer—A Review - Sumit Goyal; Gyanendra Kumar Goyal (Critical Reviews in Food Science and Nutrition, 2016)

Loop-mediated isothermal amplification (LAMP) based method for rapid and sensitive detection of ‘Candidatus Liberibacter asiaticus’ in citrus and the psyllid vector, Diaphorina citri Kuwayama - Dilip Kumar Ghosh; Sumit Bhose; Ashish Warghane; Manali Motghare; Ashwani Kumar Sharma; Arun Kumar Dhar; Siddarame Gowda (Journal of Plant Biochemistry and Biotechnology, 2016)

Fruit ripening mutants reveal cell metabolism and redox state during ripening - Vinay Kumar; Mohammad Irfan; Sumit Ghosh; Niranjan Chakraborty; Subhra Chakraborty; Asis Datta (Protoplasma, 2016)

M agnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)
Summary Pathogens encounter and metabolize a range of host‐derived metabolites while proliferating inside the host. Our understanding of these metabolites and their metabolic processes has remained largely incomplete. We investigated the role of the M agnaporthe oryzae N ‐acetylglucosamine ( GlcNAc ) catabolic pathway during rice infection. The catabolic pathway is composed of a GlcNAc transporter ( MoNgt1 ), hexokinase(s), a GlcNAc ‐6‐phosphate deacetylase ( MoDac ) and a GlcN ‐6‐phosphate deaminase ( MoDeam ). A detailed characterization of the Δ mongt1 , Δ modac and Δ modeam null mutants revealed that a defect in GlcNAc catabolism impairs the pathogenicity of M . oryzae . These mutants showed severely reduced virulence in susceptible rice cultivar due to their inability to neutralize host‐derived reactive oxygen species and their failure to develop invasive hyphal growth within the host tissue. Interestingly, during oxidative stress, M . oryzae proliferated efficiently in GlcNAc ‐containing media compared with other sugars, and the expression of fungal antioxidant genes was upregulated following GlcNAc treatment. However, GlcNAc inhibited the growth of the Δ modac and Δ modeam mutants, and this growth inhibition was enhanced during oxidative stress. These results suggest that GlcNAc helps fungus to overcome oxidative stress inside its host, perhaps by activating an antioxidant defence. In the absence of a functional catabolic pathway, GlcNAc becomes toxic to the cells.

Isolation of genes conferring salt tolerance from Piriformospora indica by random overexpression in Escherichia coli - Sunayna Gahlot; Amita Joshi; Pratap Singh; Renu Tuteja; Meenakshi Dua; Abhimanyu Jogawat; Manoj Kumar; Sumit Raj; Vikram Dayaman; Atul Kumar Johri; Narendra Tuteja (World Journal of Microbiology and Biotechnology, 2015)

Protective Effect of Spermidine Against Excitotoxic Neuronal Death Induced by Quinolinic Acid in Rats: Possible Neurotransmitters and Neuroinflammatory Mechanism - Sumit Jamwal; Shamsher Singh; Navneet Kaur; Puneet Kumar (Neurotoxicity Research, 2015)

The Ecology and Control of Potato Whitegrubs of India - R. S. Chandel; Mandeep Pathania; K. S. Verma; Badal Bhatacharyya; Sumit Vashisth; Vinod Kumar (Potato Research, 2015)

Formulation and Performance of Danazol Nano-crystalline Suspensions and Spray Dried Powders - Sumit Kumar; Rajan Jog; Jie Shen; Banu Zolnik; Nakissa Sadrieh; Diane J. Burgess (Pharmaceutical Research, 2015)

Molecular docking and biological evaluation of hydroxy-substituted (Z)-3-benzylideneindolin-2-one chalcones for the lead identification as tyrosinase inhibitors - Sharad Kumar Suthar; Vaibhav Aggarwal; Monika Chauhan; Ankesh Sharma; Sumit Bansal; Manu Sharma (Medicinal Chemistry Research, 2015)

Callus culture and in vitro biosynthesis of echitamine from Alstonia scholaris (L.) R. Br. - Sumit Kumar Singh; Trapti Joshi; Sanjeev Kanojiya; Vineeta Tripathi; Dipak Kumar Mishra (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Sun-Sky Radiometer Synthesis of Interplay Between Aerosols and Monsoon Activity Over Pune, India - P. C. S. Devara; Sumit Kumar; K. Vijayakumar; G. Pandithurai (Pure and Applied Geophysics, 2014)

Heavy metals induce oxidative stress and genome-wide modulation in transcriptome of rice root - Sonali Dubey; Manju Shri; Prashant Misra; Deepika Lakhwani; Sumit Kumar Bag; Mehar H. Asif; Prabodh Kumar Trivedi; Rudro Deo Tripathi; Debasis Chakrabarty (Functional & Integrative Genomics, 2014)

An efficient in vitro regeneration system of fieldpea (Pisum sativum L.) via. shoot organogenesis - Alok Das; Sumit Kumar; P. Nandeesha; Indu Singh Yadav; Jyoti Saini; S. K. Chaturvedi; Subhojit Datta (Journal of Plant Biochemistry and Biotechnology, 2014)

Genome-wide identification and expression analysis of the mitogen-activated protein kinase gene family from banana suggest involvement of specific members in different stages of fruit ripening - Mehar Hasan Asif; Deepika Lakhwani; Sumya Pathak; Sweta Bhambhani; Sumit K. Bag; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2014)

Ultrasound promoted green synthesis of spiro[pyrano[2,3-c]pyrazoles] as antioxidant agents - Anshu Dandia; Deepti Saini; Sumit Bhaskaran; Dinesh Kumar Saini (Medicinal Chemistry Research, 2014)

Existence of torsional surface waves in an earth’s crustal layer lying over a sandy mantle - SUMIT KUMAR VISHWAKARMA; SHISHIR GUPTA (Journal of Earth System Science, 2013)

Impact of salt exposure on N-acetylgalactosamine-4-sulfatase (arylsulfatase B) activity, glycosaminoglycans, kininogen, and bradykinin - Kumar Kotlo; Sumit Bhattacharyya; Bo Yang; Leonid Feferman; Shah Tejaskumar; Robert Linhardt; Robert Danziger; Joanne K. Tobacman (Glycoconjugate Journal, 2013)

Comparison between urban aerosol products retrieved from collocated Cimel and Prede Sun/sky radiometers at Pune, India - P. C. S. Devara; Sumit Kumar; G. Pandithurai; P. D. Safai; S. Dipu (Meteorology and Atmospheric Physics, 2013)

Design, synthesis, antimicrobial, anticancer evaluation, and QSAR studies of 4-(substituted benzylidene-amino)-1,5-dimethyl-2-phenyl-1,2-dihydropyrazol-3-ones - Sumit Sigroha; Balasubramanian Narasimhan; Pradeep Kumar; Anurag Khatkar; Kalavathy Ramasamy; Vasudevan Mani; Rakesh Kumar Mishra; Abu Bakar Abdul Majeed (Medicinal Chemistry Research, 2012)

Multicomponent diffusion in garnets I: general theoretical considerations and experimental data for Fe–Mg systems - Sascha André Borinski; Ulrich Hoppe; Sumit Chakraborty; Jibamitra Ganguly; Santanu Kumar Bhowmik (Contributions to Mineralogy and Petrology, 2012)

Development and characterization of genomic and expressed SSRs for levant cotton (Gossypium herbaceum L.) - Satya Narayan Jena; Anukool Srivastava; Krishan Mohan Rai; Alok Ranjan; Sunil K. Singh; Tarannum Nisar; Meenal Srivastava; Sumit K. Bag; Shrikant Mantri; Mehar Hasan Asif; Hemant Kumar Yadav; Rakesh Tuli; et al. (Theoretical and Applied Genetics, 2012)

Enumeration of methanogens with a focus on fluorescence in situ hybridization - Sanjay Kumar; Sumit Singh Dagar; Ashok Kumar Mohanty; Sunil Kumar Sirohi; Monica Puniya; Ramesh C. Kuhad; K. P. S. Sangu; Gareth Wyn Griffith; Anil Kumar Puniya (The Science of Nature, 2011)

Factors affecting rumen methanogens and methane mitigation strategies - Sanjay Kumar; Anil Kumar Puniya; Monica Puniya; Sumit Singh Dagar; Sunil Kumar Sirohi; Kishan Singh; Gareth Wyn Griffith (World Journal of Microbiology and Biotechnology, 2009)

Enhanced immune response of DNA vaccine (VP1-pCDNA) adsorbed on cationic PLG for foot and mouth disease in guinea pigs - Sumit Choudary; P. Ravikumar; C. Ashok Kumar; V. V. S. Suryanarayana; G. R. Reddy (Virus Genes, 2008)

Isolation and characterization of new compounds from seeds of Nigella sativa - Bhupendra Kumar Mehta; Uma Sharma; Sumit Agrawal; Vikas Pandit; Nidhi Joshi; Meenal Gupta (Medicinal Chemistry Research, 2008)

Evaluation of pentachlorophenol-degrading potentiality of Pseudomonas sp. in a soil microcosm - Sumit Kumar Gautam; Rajeev Sharma; A.H. Ahmad; Indu Shekhar Thakur (World Journal of Microbiology and Biotechnology, 2003)